Optical laminate and image display device
The optical laminate addresses in-plane variations in retardation by using a polyvinyl alcohol resin film polarizer and protective layers with controlled properties, ensuring consistent performance and durability in image display devices.
Patent Information
- Application Number
- JP2024179143
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-27
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-27
AI Technical Summary
Conventional optical laminates experience significant in-plane variations in retardation values when exposed to high temperatures, which affect the performance and visibility of image display devices.
The optical laminate is designed with specific layer configurations and material properties, including a polyvinyl alcohol resin film polarizer, protective layers with controlled tensile modulus and thickness, and a retardation film, to minimize in-plane variations in retardation values under high temperatures.
The solution effectively suppresses in-plane variations in retardation, enhancing the antireflection performance and durability of image display devices by maintaining consistent optical properties across temperature changes.
Smart Images

Figure 2024180789000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate and an image display device including the optical laminate. [Background technology]
[0002] In image display devices such as organic EL display devices, it is known that a circular polarizing plate is used to improve anti-reflection performance in order to suppress a decrease in visibility due to reflection of external light (for example, Patent Document 1). The circular polarizing plate is an optical laminate including a polarizer and a retarder. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-121862 A Summary of the Invention [Problem to be solved by the invention]
[0004] Conventional optical laminates have a problem in that the in-plane variation in the amount of change in the in-plane retardation value when placed under high temperature is large. An object of the present invention is to provide an optical laminate including a polarizer and a retarder, in which the in-plane variation is suppressed, and an image display device including the optical laminate. [Means for solving the problem]
[0005] The present invention provides the following: [1] An optical laminate comprising a first protective layer, a polarizer, a second protective layer, and a retarder in this order, the polarizer is a polyvinyl alcohol-based resin film having a thickness of 15 μm or less and having a dichroic dye adsorbed and oriented therein; When the tensile modulus of elasticity of the second protective layer at a temperature of 85° C. is E2 [MPa] and the thickness is T2 [μm], the following formula (i): E2×T2≦16000 (i) An optical laminate that satisfies the above requirements. [2] The optical laminate according to [1], wherein the value of E2×T2 is 1850 or less. [3] The optical laminate according to [1] or [2], wherein the retarder includes a retardation film. [4] The following formula (ii): T2≦7 (ii) The optical laminate according to any one of [1] to [3], further satisfying the above. [5] The moisture permeability of the second protective layer is 1700 g / m 2 The optical laminate according to any one of [1] to [4], wherein the wavelength is 1 / 24 hr or less. [6] The optical laminate according to any one of [1] to [5], wherein the second protective layer is made of a cyclic polyolefin resin. [7] The optical laminate according to any one of [1] to [6], wherein the second protective layer has an in-plane retardation value of 10 nm or less at a wavelength of 550 nm. [8] The optical laminate according to any one of [1] to [7], further comprising an adhesive layer between the polarizer and the second protective layer. [9] The optical laminate according to any one of [1] to [8], wherein the polarizer has a boron content of 0.5% by mass or more and 5.5% by mass or less.
[10] When the tensile modulus of the first protective layer at a temperature of 85° C. is E1 [MPa] and the thickness is T1 [μm], the following formula (iii): 17000≦E1×T1≦40000 (iii) The optical laminate according to any one of [1] to [9], which satisfies the above.
[11] The optical laminate according to any one of [1] to
[10] , further comprising a pressure-sensitive adhesive layer laminated on the side of the retarder opposite to the second protective layer side.
[12] When the tensile modulus of a laminate from a layer adjacent to the surface of the polarizer on the side of the retarder in the polarizer to a layer adjacent to the surface of the pressure-sensitive adhesive layer on the side of the retarder in the laminate at a temperature of 23° C. is E3 [MPa] and the thickness is T3 [μm], the following formula (iv) is obtained: 7000≦E3×T3≦22000 (iv) The optical laminate according to
[11] , which satisfies the above.
[13] An image display device comprising the optical laminate according to any one of [1] to
[12] . Effect of the Invention
[0006] It is possible to provide an optical laminate including a polarizer and a retarder, in which the in-plane variation is suppressed, and an image display device including the optical laminate. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a layer structure of an optical laminate according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of the layer structure of the optical laminate according to the present invention. [Diagram 3] FIG. 13 is a schematic top view showing a method for preparing a measurement sample for measuring the tensile modulus E3 of the laminate α. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiment. All the drawings are shown to help understand the present invention, and the size and shape of each component shown in the drawings do not necessarily correspond to the size and shape of the actual component.
[0009] <Optical laminate> (1) Overview FIG. 1 is a schematic cross-sectional view showing an example of the layer structure of an optical laminate according to the present invention (hereinafter, also simply referred to as "optical laminate"). The optical laminate shown in FIG. 1 includes a first protective layer 10, a polarizer 5, a second protective layer 20, and a retarder 30, in this order. The optical laminate can be suitably used as a circular polarizer. The term "circular polarizer" includes an elliptical polarizer. The optical laminate can be used as an anti-reflection film or the like in an image display device such as an organic electroluminescence (organic EL) display device.
[0010] 1 includes a first adhesive layer 41 between the first protective layer 10 and the polarizer 5. The first protective layer 10 and the first adhesive layer 41 are preferably in direct contact with each other, and the first adhesive layer 41 and the polarizer 5 are preferably in direct contact with each other. The optical laminate according to the present invention may not have the first adhesive layer 41, and in this case, the first protective layer 10 and the polarizer 5 are in direct contact with each other.
[0011] 1 includes a second adhesive layer 42 between the polarizer 5 and the second protective layer 20. The polarizer 5 and the second adhesive layer 42 are preferably in direct contact with each other, and the second adhesive layer 42 and the second protective layer 20 are preferably in direct contact with each other. The optical laminate according to the present invention may not have the second adhesive layer 42, and in this case, the polarizer 5 and the second protective layer 20 are in direct contact with each other.
[0012] 1 includes a third adhesive layer 43 between the second protective layer 20 and the retarder 30. The second protective layer 20 and the third adhesive layer 43 are preferably in direct contact with each other, and the third adhesive layer 43 and the retarder 30 are preferably in direct contact with each other.
[0013] Fig. 2 is a schematic cross-sectional view showing another example of the layer structure of the optical laminate according to the present invention. The optical laminate shown in Fig. 2 has the same layer structure as the optical laminate shown in Fig. 1, except that it further includes a pressure-sensitive adhesive layer 50 laminated on the side of the retarder 30 opposite to the second protective layer 20.
[0014] In the optical laminate according to the present invention, the polarizer 5 is a polyvinyl alcohol-based resin film having a thickness of 15 μm or less in which a dichroic dye is adsorbed and oriented. When the tensile modulus of elasticity of the second protective layer 20 at a temperature of 85° C. is E2 [MPa] and the thickness is T2 [μm], the following formula (i): E2×T2≦16000 (i) According to the present invention, it is possible to provide an optical laminate in which the in-plane variation in the amount of change in the in-plane retardation value when placed under high temperature (hereinafter also referred to as "in-plane variation in the amount of change in retardation") is suppressed. This is believed to be because, when the polarizer shrinks due to heat, tensile stress is applied to the second protective layer and thus to the retarder 30, and since the second protective layer satisfies formula (i), the tensile stress is unlikely to concentrate on the end of the second protective layer and thus to the end of the retarder 30. Hereinafter, elements that constitute or can constitute the optical laminate will be described in detail.
[0015] (2) Polarizer The polarizer 5 is an optical film (linear polarizer) that transmits linearly polarized light having a vibration plane perpendicular to the absorption axis when unpolarized light is incident on the polarizer 5. Specifically, the polarizer 5 is a polyvinyl alcohol-based resin film (hereinafter also referred to as a "PVA-based film") in which a dichroic dye is adsorbed and oriented.
[0016] The polyvinyl alcohol resin (hereinafter also referred to as "PVA resin") constituting the PVA film can be produced by saponifying a polyvinyl acetate resin. The polyvinyl acetate resin can be a copolymer of vinyl acetate and another monomer copolymerizable with vinyl acetate, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group. In this specification, "(meth)acrylic" means either acrylic or methacrylic. The "(meth)" in (meth)acrylate has the same meaning.
[0017] The saponification degree of the PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the PVA resin is usually about 1000 to 10000, preferably about 1500 to 5000. The average polymerization degree of the PVA resin can be determined in accordance with JIS K 6726 (1994). If the average polymerization degree is less than 1000, it is difficult to obtain a preferable polarizing performance, and if it exceeds 10000, the film processability may be poor.
[0018] A polarizer is usually produced through a process of uniaxially stretching a PVA-based film, a process of dyeing the PVA-based film with a dichroic dye to adsorb the dichroic dye, a process of treating the PVA-based film with the adsorbed dichroic dye with an aqueous boric acid solution to crosslink the film, and a process of washing the film with water after the crosslinking treatment with the aqueous boric acid solution (hereinafter also referred to as boric acid treatment).
[0019] The uniaxial stretching of the PVA-based film can be carried out before, simultaneously with, or after dyeing with a dichroic dye. If the uniaxial stretching is carried out after dyeing, it can be carried out before or during the boric acid treatment. Of course, the uniaxial stretching can be carried out in multiple stages as shown here. For the uniaxial stretching, the film can be conveyed between rolls with different peripheral speeds. A method of uniaxially stretching in the film conveying direction using a heat roll, a method of uniaxially stretching in the film conveying direction using a tenter, or a method of stretching in the width direction using a tenter can be used. The uniaxial stretching may be performed by dry stretching in the air, or by wet stretching in a swollen state using a solvent such as water. The stretching ratio is usually about 3 to 8 times.
[0020] Dyeing of a PVA-based film with a dichroic dye can be carried out, for example, by immersing the PVA-based film in an aqueous solution containing the dichroic dye. As the dichroic dye, specifically, iodine or a dichroic organic dye is used. It is preferable that the PVA-based film is immersed in water and swelled before the dyeing process.
[0021] When iodine is used as the dichroic dye, a method of dyeing a PVA-based film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water, and the content of potassium iodide is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is usually about 20 to 1,800 seconds.
[0022] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of immersing a PVA-based film in an aqueous solution containing a water-soluble dichroic organic dye is usually used for dyeing. The content of the dichroic organic dye in this aqueous solution is usually about 0.0001 to 10 parts by mass, preferably 0.001 to 1 part by mass, per 100 parts by mass of water. This aqueous dye solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the aqueous dichroic organic dye solution used for dyeing is usually about 20 to 80°C. The immersion time in this aqueous solution (dyeing time) is usually about 10 to 1,800 seconds.
[0023] The boric acid treatment after dyeing with a dichroic dye can be carried out by immersing the dyed PVA-based film in a boric acid-containing aqueous solution. The content of boric acid in the boric acid-containing aqueous solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, the boric acid-containing aqueous solution preferably contains potassium iodide. The content of potassium iodide in the boric acid-containing aqueous solution is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the boric acid-containing aqueous solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid-containing aqueous solution is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0024] The PVA-based film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the boric acid-treated PVA-based film in water. The temperature of the water in the washing is usually about 5 to 40° C. The immersion time is usually about 1 to 120 seconds.
[0025] After washing with water, the polarizer is obtained by drying. The drying can be performed using a hot air dryer or a far infrared heater. The temperature of the drying is usually about 30 to 100°C, and preferably 50 to 80°C. The time of the drying is usually about 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content in the polarizer is reduced to a practical level by the drying. The moisture content is usually about 5 to 20 mass% and preferably 8 to 15 mass% with respect to the total mass of the polarizer. When the moisture content is 5 mass% or more, the polarizer has sufficient flexibility, and therefore, damage or breakage after drying can be suppressed. When the moisture content is 20 mass% or less, the polarizer has sufficient thermal stability.
[0026] In this manner, a polarizer in which a dichroic dye is adsorbed and oriented on a PVA-based film can be produced.
[0027] The luminosity-corrected polarization degree Py of the polarizer is usually 95% or more, preferably 97% or more, more preferably 98% or more, even more preferably 98.7% or more, still more preferably 99.0% or more, particularly preferably 99.4% or more, and may be 99.9% or more. The luminosity-corrected polarization degree Py of the polarizer may be 99.99% or less. The luminosity-corrected polarization degree Py can be calculated by performing luminosity correction on the obtained polarization degree using a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation) with a 2-degree visual field (C light source) according to "JIS Z 8701".
[0028] Increasing the luminosity-corrected polarization degree Py of the polarizer is advantageous in terms of improving the function of the optical laminate as an antireflection film and the durability of the optical laminate. If the luminosity-corrected polarization degree Py of the polarizer is less than 95%, the polarizer may not function as an antireflection film.
[0029] The polarizer has a boron content of preferably 0.5% by mass or more, more preferably 1.5% by mass or more, even more preferably 2.5% by mass or more, and particularly preferably 2.7% by mass or more. By having a boron content of 0.5% by mass or more, the dichroic dye can be stably held, and the effect of suppressing the decrease in the polarization degree of the polarizer and the effect of improving the durability of the optical laminate can be expected. The higher the boron content, the higher the ability to hold the dichroic dye tends to be. In addition, the boron content of the polarizer is preferably 5.5% by mass or less, more preferably 5.0% by mass or less, even more preferably 4.5% by mass or less, even more preferably 4.2% by mass or less, and particularly preferably 4.0% by mass or less. When the boron content is within this range, the in-plane variation of the retardation change amount can be more effectively suppressed. The lower the boron content, the easier it is to suppress the in-plane variation of the retardation change amount.
[0030] The boron content in the polarizer can be determined, for example, by dissolving a given mass of the polarizer in an aqueous mannitol solution and titrating the solution with an aqueous NaOH solution. The method for measuring the boron content in the polarizer will be described in detail in the section [Examples].
[0031] The boron content of the polarizer can be controlled by adjusting the boric acid concentration of the aqueous boric acid solution used in the boric acid treatment or by controlling the degree to which the aqueous boric acid solution is washed off in the washing step.
[0032] The thickness of the polarizer is 15 μm or less, preferably 13 μm or less, more preferably 10 μm or less. When the thickness of the polarizer is within this range, it is advantageous to make the optical laminate thin, and the in-plane variation of the retardation change amount can be more effectively suppressed. The thickness of the polarizer is usually 2 μm or more, preferably 3 μm or more, and may be, for example, 5 μm or more.
[0033] (3) First protective layer The first protective layer 10 has a function of protecting the surface of the polarizer 5. The first protective layer 10 may be laminated in direct contact with the surface of the polarizer 5, or may be laminated via a first pressure-sensitive adhesive layer 41. The first protective layer 10 may be subjected to a surface treatment (e.g., corona treatment, etc.) in order to improve adhesion to the polarizer 5, and may have a thin layer such as a primer layer (also referred to as an easy-adhesion layer) formed thereon.
[0034] The first protective layer 10 has a tensile modulus of elasticity E1 [MPa] at a temperature of 85° C. and a thickness T1 [μ m], the following formula (iii): 17000≦E1×T1≦40000 (iii) It is preferable that the following is satisfied.
[0035] When the first protective layer 10 satisfies the formula (iii), the in-plane variation in the amount of change in retardation can be more effectively suppressed. This is believed to be because the tensile stress caused by the shrinkage of the polarizer due to heat is less likely to concentrate on the end of the retarder 30. From the viewpoint of suppressing the in-plane variation in the amount of change in retardation, the value of E1×T1 on the left side of the formula (iii) is more preferably 18000 or more, and even more preferably 20000 or more. From the viewpoint of suppressing curling of the entire polarizing plate under a durable environment, the value of E1×T1 is more preferably 35000 or less, even more preferably 30000 or less, and particularly preferably 25000 or less.
[0036] The thickness T1 of the first protective layer is usually 60 μm or less, and from the viewpoint of suppressing curling of the entire polarizing plate under a durable environment, it is preferably 50 μm or less, more preferably 40 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.
[0037] The tensile modulus E1 of the first protective layer at a temperature of 85° C. is usually 2000 MPa or less, preferably 1500 MPa or less, more preferably 1000 MPa or less, and usually 100 MPa or more, preferably 200 MPa or more, more preferably 300 MPa or more. The tensile modulus E1 can be measured according to the description in the [Examples] section.
[0038] For example, a resin film having excellent transparency, mechanical strength, thermal stability, moisture blocking properties, isotropy, stretchability, etc. can be used as the first protective layer. The resin film may be a thermoplastic resin film. Specific examples of such thermoplastic resins include: Cellulose ester resins such as triacetyl cellulose; Polyester resins such as polyethylene terephthalate and polyethylene naphthalate; Polyethersulfone resin; Polysulfone resin; Polycarbonate-based resins; Polyamide resins such as nylon and aromatic polyamides; Polyimide resin; Linear polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; Cyclic polyolefin resins having cyclo- and norbornene structures (also called norbornene resins); (Meth)acrylic resins such as polymethyl methacrylate; Polyarylate resins; Polystyrene resin; Polyvinyl alcohol resin, As well as mixtures thereof. The protective film made of the above thermoplastic resin may be commercially available.
[0039] Examples of linear polyolefin resins include linear olefin homopolymers such as polyethylene resins (polyethylene resins which are homopolymers of ethylene, and copolymers mainly composed of ethylene) and polypropylene resins (polypropylene resins which are homopolymers of propylene, and copolymers mainly composed of propylene), as well as copolymers composed of two or more types of linear olefins.
[0040] The cyclic polyolefin resin is a general term for resins polymerized using cyclic olefins as polymerization units. For example, see JP-A-1-240517, JP-A-3-14882, Examples of the cyclic polyolefin resin include the resins described in JP-A-3-122137. Specific examples of the cyclic polyolefin resin include ring-opening (co)polymers of cyclic olefins, addition polymers of cyclic olefins, copolymers (typically random copolymers) of cyclic olefins with chain olefins such as ethylene and propylene, graft polymers modified with unsaturated carboxylic acids or derivatives thereof, and hydrogenated products thereof. Among these, norbornene resins using norbornene monomers such as norbornene or polycyclic norbornene monomers as the cyclic olefin are preferably used.
[0041] The polyester resin is a resin having an ester bond in the main chain, and is generally a polycondensate of a polyvalent carboxylic acid or its derivative and a polyhydric alcohol. As the polyvalent carboxylic acid or its derivative, a divalent dicarboxylic acid or its derivative can be used, such as terephthalic acid, isophthalic acid, dimethyl terephthalate, dimethyl naphthalenedicarboxylate, etc. As the polyhydric alcohol, a divalent diol can be used, such as ethylene glycol, propanediol, butanediol, neopentyl glycol, cyclohexanedimethanol, etc. A representative example of the polyester resin is polyethylene terephthalate, which is a polycondensate of terephthalic acid and ethylene glycol.
[0042] The cellulose ester resin is an ester of cellulose and fatty acid. Specific examples of the cellulose ester resin include cellulose triacetate, cellulose diacetate, cellulose tripropionate, and cellulose dipropionate. In addition, copolymers having a plurality of polymerization units constituting these cellulose ester resins and those in which a part of hydroxyl groups is modified with other substituents are also included. Among these, cellulose triacetate (triacetyl cellulose) is particularly preferred.
[0043] The (meth)acrylic resin is a resin whose main constituent monomer is a compound having a (meth)acryloyl group. Specific examples of the (meth)acrylic resin include poly(meth)acrylic acid ester such as polymethyl methacrylate; methyl methacrylate-(meth)acrylic acid copolymer; methyl methacrylate-(meth)acrylic acid ester copolymer; methyl methacrylate-acrylic acid ester-(meth)acrylic acid copolymer; methyl (meth)acrylate-styrene copolymer (MS resin, etc.); copolymers of methyl methacrylate and compounds having alicyclic hydrocarbon groups (e.g., methyl methacrylate-cyclohexyl methacrylate copolymer, methyl methacrylate-norbornyl (meth)acrylate copolymer, etc.). Preferably, a polymer whose main component is poly(meth)acrylic acid C1-C6 alkyl ester such as polymethyl (meth)acrylate is used, and more preferably, a methyl methacrylate resin whose main component is methyl methacrylate (50 to 100 mass%, preferably 70 to 100 mass%) is used.
[0044] The polycarbonate-based resin is composed of a polymer in which monomer units are bonded via carbonate groups. The polycarbonate-based resin may be a resin called a modified polycarbonate in which the polymer skeleton is modified, or a copolymer polycarbonate.
[0045] The first protective layer may be a film containing the thermoplastic resin that has been stretched. Examples of the stretching treatment include uniaxial stretching and biaxial stretching. Examples of the stretching direction include the machine direction (MD) of the unstretched film, a direction perpendicular thereto (TD), and a direction oblique to the machine direction (MD). The biaxial stretching may be simultaneous biaxial stretching in which the film is stretched in two stretching directions at the same time, or sequential biaxial stretching in which the film is stretched in a predetermined direction and then stretched in the other direction. The stretching treatment may be performed, for example, by stretching in the longitudinal direction (machine direction: MD) using two or more pairs of nip rolls with a high peripheral speed on the outlet side, or by gripping both side ends of the unstretched film with chucks and spreading it in the direction perpendicular to the machine direction (TD). In this case, the retardation value and wavelength dispersion can be adjusted by adjusting the thickness of the film or the stretching ratio. It is also possible to control the wavelength dispersion value by adding a wavelength dispersion adjusting agent to the resin.
[0046] The first protective layer may contain any suitable additive depending on the purpose. Examples of the additive include antioxidants such as hindered phenols, phosphorus, and sulfur, stabilizers such as light stabilizers, ultraviolet absorbers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic and inorganic fillers; resin modifiers; plasticizers; lubricants; and retardation reducers. The types, combinations, and contents of the additives contained may be appropriately set depending on the purpose and desired properties.
[0047] In addition, in order to impart desired surface optical properties or other characteristics, a coating layer (surface treatment layer) can be provided on the outer surface of the first protective layer. Specific examples of the surface treatment layer include a hard coat layer, an antiglare layer, an antireflection layer, an antistatic layer, and an antifouling layer. The method for forming the surface treatment layer is not particularly limited, and a known method can be used. The surface treatment layer may be formed on one surface or both surfaces of the first protective layer.
[0048] The hard coat layer has a function of increasing the surface hardness of the first protective layer, and is provided for the purpose of preventing surface scratches, etc. The hard coat layer preferably has a pencil hardness of H or harder, as measured by a pencil hardness test (measured by placing a protective film having a hard coat layer on a glass plate) specified in JIS K 5600-5-4:1999 "General test methods for paints - Part 5: Mechanical properties of coatings - Section 4: Scratch hardness (pencil method)".
[0049] The material for forming the hard coat layer is generally cured by heat or light. For example, organic hard coat materials such as organic silicone, melamine, epoxy, (meth)acrylic, and urethane (meth)acrylate, and inorganic hard coat materials such as silicon dioxide can be mentioned. Among these, urethane (meth)acrylate or polyfunctional (meth)acrylate hard coat materials are preferably used because they have good adhesion to the protective film and are excellent in productivity.
[0050] If desired, the hard coat layer may contain various fillers for the purpose of adjusting the refractive index, improving the flexural modulus, stabilizing the volume shrinkage rate, and further improving heat resistance, antistatic properties, antiglare properties, etc. The hard coat layer may also contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, leveling agents, and defoamers.
[0051] The hard coat layer may contain an additive to further improve its strength. The additive is not limited, and examples thereof include inorganic fine particles, organic fine particles, and mixtures thereof. The thickness of the hard coat layer is preferably thicker in order to provide hardness, but if it is too thick, it is likely to break when cut, so it may be 1 μm to 20 μm, or 2 μm to 10 μm. The thickness of the hard coat layer is preferably 3 μm to 7 μm.
[0052] The antiglare layer is a layer having a fine uneven surface, and is preferably formed using the above-mentioned hard coat material.
[0053] An anti-glare layer having a finely uneven surface can be formed by, for example, 1) forming a coating film containing fine particles on a protective film and providing unevenness based on the fine particles, or 2) forming a coating film, which may or may not contain fine particles, on a protective film, and then pressing the film against a mold (such as a roll) that has been given an uneven surface to transfer the uneven surface (also known as an embossing method).
[0054] The anti-reflection layer is a layer for weakening the reflection of external light on the surface of the protective film for a person observing the protective film, and usually has a reflectance of 1.5% or less for visible light. An anti-reflection layer with such a reflectance is typically formed by laminating a high refractive index layer having a high refractive index and a low refractive index layer having a low refractive index, or by using the method and materials described in JP 2021-6929 A. By adjusting these refractive indices and the thickness of each layer, the reflected light from each layer can be weakened by each other, and excellent anti-reflection function is achieved.
[0055] As described in detail later, it is preferable to manufacture the antireflection layer consisting of a high refractive index layer and a low refractive index layer using a coating composition capable of forming each of the high refractive index layer and the low refractive index layer, since the operation is extremely simple. Here, an example of a coating composition capable of forming each of the high refractive index layer and the low refractive index layer will be given. Such a coating composition is liquid and contains an appropriate curable resin and, if necessary, an additive. A coating composition capable of forming a high refractive index layer (a composition for forming a high refractive index layer) is, for example, a curable resin such as urethane acrylate, and an initiator (photopolymerization initiator) for photopolymerization such as acetophenone, benzophenone, benzyl dimethyl ketal, α-hydroxyalkylphenone, α-aminoalkylphenone, or thioxanthone, dissolved in a solvent such as methyl ethyl ketone or methyl isobutyl ketone. In order to improve the coating property, a leveling agent, preferably a fluorine-based leveling agent, may be included. In addition, as a coating composition capable of forming a low refractive index layer (composition for forming a low refractive index layer), a binder resin such as polyethylene glycol diacrylate or pentaerythritol (tri / tetra)acrylate as a curable resin is used, and an initiator for photopolymerization (photopolymerization initiator) such as acetophenone, benzophenone, benzyl dimethyl ketal, α-hydroxyalkylphenone, α-aminoalkylphenone, or thioxanthone is dissolved in a solvent such as 1-methoxy-2-propyl acetate or methyl isobutyl, and silica particles are dispersed in the solution. In order to improve the coating property, a fluorine-based leveling agent may be included. Note that the coating compositions capable of forming the high refractive index layer and the low refractive index layer listed here are merely examples, and it is preferable to optimize the composition for forming a high refractive index layer and the composition for forming a low refractive index layer, respectively, depending on the characteristics of the antireflection layer to be formed.
[0056] The antireflection layer may, for example, include a low refractive index layer, or may have a multi-layer structure further including a high refractive index layer and / or a medium refractive index layer between the protective film and the low refractive index layer.
[0057] The low refractive index layer can be formed by applying a coating liquid containing a cured product of the above-mentioned curable resin, a light-transmitting resin such as a metal alkoxide polymer, and inorganic particles, and then curing the coating layer as necessary. Examples of inorganic particles include low refractive index particles such as LiF (refractive index 1.4), MgF (refractive index 1.4), 3NaF·AlF (refractive index 1.4), AlF (refractive index 1.4), and Na3AlF6 (refractive index 1.33), and hollow silica particles.
[0058] The antistatic layer is provided for the purpose of imparting electrical conductivity to the surface of the first protective layer and suppressing the effects of static electricity. For example, a method of applying a resin composition containing a conductive substance (antistatic agent) onto the first protective layer can be used to form the antistatic layer. For example, an antistatic hard coat layer can be formed by adding an antistatic agent to the hard coat material used to form the hard coat layer described above.
[0059] The antifouling layer is provided to impart water repellency, oil repellency, sweat resistance, antifouling properties, etc. A suitable material for forming the antifouling layer is a fluorine-containing organic compound. Examples of the fluorine-containing organic compound include fluorocarbon, perfluorosilane, and polymer compounds thereof. The antifouling layer can be formed by a physical vapor deposition method, typically vapor deposition or sputtering, a chemical vapor deposition method, a wet coating method, or the like, depending on the material to be formed. The average thickness of the antifouling layer is usually about 1 to 50 nm, and preferably 3 to 35 nm.
[0060] When the optical laminate is applied to an image display device, the diffusion of the dichroic dye such as iodine in the polarizer 5 may cause corrosion of metal members (electrodes, etc.) present near the optical laminate in the image display device. This is due to the migration of the dichroic dye such as iodine to the metal members due to the diffusion. In order to suppress the corrosion of the metal members, it is preferable to suppress the amount of the dichroic dye migrating to the metal members. By not providing a coating layer (surface treatment layer) on the outer surface of the first protective layer, the amount of the migration tends to be suppressed. This is because the dichroic dye is easily diffused and released from the first protective layer side (the viewing side), and as a result, the amount of the dichroic dye migrating from the polarizer 5 to the opposite side to the viewing side is reduced.
[0061] (4)Second protective layer The second protective layer 20 has a function of protecting the surface of the polarizer 5. The second protective layer 20 may be laminated in direct contact with the surface of the polarizer 5, or may be laminated via a second adhesive layer 42. The second protective layer 20 may be subjected to a surface treatment (e.g., corona treatment, etc.) in order to improve adhesion to the polarizer 5, and may have a thin layer such as a primer layer (also referred to as an easy-adhesion layer) formed thereon.
[0062] When the tensile modulus of elasticity at a temperature of 85° C. is E2 [MPa] and the thickness is T2 [μm], the second protective layer 20 has a thickness satisfying the following formula (i): E2×T2≦16000 (i) Meet the following.
[0063] According to the optical laminate according to the present invention, which satisfies the formula (i), the in-plane variation in the amount of change in retardation can be suppressed. This is believed to be because the tensile stress caused by the shrinkage of the polarizer due to heat is less likely to concentrate at the end of the retarder 30. Although both satisfying the formula (i) and satisfying the formula (iii) contribute to suppressing the in-plane variation in the amount of change in retardation, the contribution of the second protective layer 20 disposed between the polarizer 5 and the retarder 30 satisfying the formula (i) is greater. In addition, by disposing the second protective layer 20 between the polarizer 5 and the retarder 30, the dichroic dye such as iodine in the polarizer 5 can be prevented or suppressed from migrating to the metal member due to the diffusion. By preventing or suppressing the diffusion of the dichroic dye such as iodine, the corrosion of the metal member (electrode, etc.) present near the optical laminate in the image display device can be prevented or suppressed.
[0064] From the viewpoint of suppressing the in-plane variation of the retardation change amount, the value of the left side E2×T2 in formula (i) is preferably 12000 or less, more preferably 8000 or less, even more preferably 4000 or less, still more preferably 3000 or less, particularly preferably 2000 or less, and may be 1850 or less, 1800 or less, or 1000 or less. The value of E2×T2 is usually 100 or more, and may be 300 or more, or 500 or more.
[0065] The thickness T2 of the second protective layer is, for example, 0.1 to 60 μm, and preferably 0.2 to 30 μm. From the viewpoint of suppressing the in-plane variation in the amount of change in retardation, the thickness T2 is determined based on the following formula (ii): T2≦7 (ii) It is preferable that the thickness T2 satisfies the above. The thickness T2 is more preferably 6 μm or less, even more preferably 5 μm or less, and even more preferably 4 μm or less. The thickness T2 is, for example, 0.1 μm or more, and may be 0.5 μm or more, 1 μm or more, or 2 μm or more. From the viewpoint of suppressing the above-mentioned corrosion of the metal member, the thickness T2 is preferably 2 to 4 μm, and more preferably 3 to 4 μm.
[0066] From the viewpoint of suppressing the in-plane variation of the retardation change amount, the tensile modulus E2 of the second protective layer at a temperature of 85°C is preferably 1500 MPa or less, more preferably 1200 MPa or less, even more preferably 1100 MPa or less, even more preferably 1000 MPa or less, particularly preferably 800 MPa or less, and most preferably 500 MPa or less. The tensile modulus E2 is usually 100 MPa or more, and may be 200 MPa or more. The tensile modulus E2 can be measured according to the description in the [Example] section.
[0067] From the viewpoint of suppressing the above-mentioned corrosion of the metal member, the second protective layer has a moisture permeability of, for example, 1700 g / m 2 / 24hr or less, preferably 1500g / m 2 / 24hr or less, more preferably 1000g / m 2 / 24hr or less, more preferably 100g / m 2 / 24hr or less, and even more preferably 50g / m 2 / 24hr or less, 10g / m 2 The moisture permeability may be 1 g / m or less. 2 / 24hr or more, preferably 3g / m 2 The moisture permeability of the second protective layer can be measured according to the description in the section [Examples].
[0068] The smaller the photoelastic modulus of the second protective layer, the smaller the amount of change in retardation of the second protective layer due to the tensile stress caused by the shrinkage of the polarizer due to heat, and therefore the smaller the thickness of the second protective layer, the more advantageous it tends to be in terms of suppressing the in-plane variation in the amount of change in retardation. On the other hand, according to the present invention, the in-plane variation in the amount of change in retardation can be effectively suppressed, so that the effect of the present invention is more easily achieved when the second protective layer has photoelasticity. The photoelastic coefficient of the second protective layer is preferably 0.1×10 -12 Pa -1 ~10×10 -12 Pa -1 , more preferably 1×10 -12Pa -1 ~5×10 -12 Pa -1 The photoelastic modulus of the second protective layer can be measured according to the description in the section [Examples].
[0069] As the second protective layer, for example, a resin film having excellent transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, stretchability, etc. can be used. The resin film may be a thermoplastic resin film. Specific examples of such thermoplastic resins are the same as those described for the first protective layer. Protective films made of thermoplastic resins may be available on the market.
[0070] The thermoplastic resin constituting the thermoplastic resin film used as the second protective layer and the thermoplastic resin layer described below is preferably a cyclic polyolefin-based resin, a polyester-based resin, a polycarbonate-based resin, a (meth)acrylic resin, or a polystyrene-based resin, more preferably a cyclic polyolefin-based resin, a (meth)acrylic resin, or a polystyrene-based resin, even more preferably a cyclic polyolefin-based resin or a (meth)acrylic resin, and even more preferably a cyclic polyolefin-based resin.
[0071] The thermoplastic resin film used as the second protective layer may be a film existing alone, and in this case, the thermoplastic resin film is laminated on the polarizer 5 via the second adhesive layer 42 as necessary. Alternatively, the second protective layer may be a thermoplastic resin layer. For example, a composition containing a thermoplastic resin is applied onto a supporting substrate, and dried as necessary to obtain a thermoplastic resin layer with a supporting substrate. The thermoplastic resin layer is attached to the polarizer 5 via the second adhesive layer 42 as necessary, and then the supporting substrate is peeled off and removed, thereby laminating a thermoplastic resin layer as the second protective layer on the polarizer 5 (first method). For example, when the second protective layer 20 is a thermoplastic resin layer or a resin layer such as a cured resin layer described later, the polarizer 5 and the second protective layer 20 may be in direct contact with each other without the second adhesive layer 42.
[0072] When the second protective layer is a thermoplastic resin layer, the above composition can be directly applied to the surface of the polarizer 5 and dried as necessary to form a thermoplastic resin layer (the first In this case, the polarizer 5 and the second protective layer 20 are in direct contact with each other without the second pressure-sensitive adhesive layer 42. However, when the composition contains a solvent, the first method is preferred because it is easier to stably form a thermoplastic resin layer with a sufficiently reduced solvent content.
[0073] The second protective layer may be a cured resin layer containing a cured product of a curable resin. Examples of the curable resin include thermosetting resins and active energy curable resins, such as (meth)acrylic resins, epoxy resins, oxetane resins, urethane resins, (meth)acrylic urethane resins, and melamine resins. The cured resin layer containing a cured product of a curable resin can be formed by applying a composition containing a curable resin onto a supporting substrate, drying the composition as necessary, and then applying heat or irradiating the composition with active energy rays such as visible light, ultraviolet light, infrared light, X-rays, α rays, β rays, γ rays, and electron beams. The obtained cured resin layer with supporting substrate is attached to the polarizer 5 via the second adhesive layer 42 as necessary, and then the supporting substrate is peeled off and removed, thereby laminating the cured resin layer as the second protective layer on the polarizer 5.
[0074] From the viewpoint of suppressing in-plane variation in retardation change, the second protective layer is preferably a thermoplastic resin film or layer made of a cyclic polyolefin resin, a thermoplastic resin film or layer made of a (meth)acrylic resin, a cured resin layer containing a cured product of a (meth)acrylic resin, or a thermoplastic resin film or layer made of a polystyrene resin. In consideration of further suppressing migration of the dichroic dye in the polarizer 5 to the metal member, the second protective layer is more preferably a thermoplastic resin film or layer made of a cyclic polyolefin resin, or a thermoplastic resin film or layer made of a polystyrene resin.
[0075] The second protective layer may contain any suitable additive depending on the purpose. Specific examples of the additive are the same as those described for the first protective layer.
[0076] The second protective layer is preferably a film having no retardation property or a small retardation value. Specifically, the in-plane retardation value of the second protective layer at a wavelength of 550 nm is preferably 10 nm or less. The in-plane retardation value is 0 nm or more. In addition, the retardation value in the thickness direction of the second protective layer at a wavelength of 550 nm is preferably -10 nm to +10 nm.
[0077] (5) Phaser The retarder 30 is an optical element exhibiting retardation in the in-plane or thickness direction, and preferably includes a retardation film. The retardation film is a film exhibiting retardation in the in-plane or thickness direction, and is a layer (cured layer) made of a polymer of a polymerizable liquid crystal compound, or a combination of the layer and an alignment film. The retardation film includes, for example, a cured layer of a retardation film-forming composition containing a polymerizable liquid crystal compound.
[0078] When the retarder 30 includes a retardation film, the dichroic dye migrates to the metal member, which easily causes the corrosion of the metal member, but according to the present invention, the corrosion can be effectively suppressed even when the retarder 30 includes a retardation film. Furthermore, when the retarder 30 includes a retardation film, this is advantageous for making the optical laminate thinner, and when the retarder 30 includes a retardation film, this is preferable in that the wavelength dispersion characteristics can be arbitrarily designed.
[0079] (5-1) Retardation film A retardation film is usually formed by applying a composition for forming a retardation film onto an alignment film formed on a substrate, and polymerizing the polymerizable liquid crystal compound contained in the composition for forming a retardation film. A retardation film is usually a film in which the polymerizable liquid crystal compound is cured in an aligned state, and in order to generate a retardation in the viewing plane, it is necessary for the polymerizable liquid crystal compound to be a cured film in which the polymerizable group is polymerized in a state in which the polymerizable liquid crystal compound is aligned horizontally to the substrate surface. At this time, the polymerizable liquid crystal compound is formed into rod-shaped liquid crystals. If the polymerizable liquid crystal compound is a discotic liquid crystal, the plate may be a positive A plate. If the polymerizable liquid crystal compound is a discotic liquid crystal, the plate may be a negative A plate.
[0080] The retarder may include two or more retardation films having different optical anisotropy. In order to achieve a high degree of anti-reflection function, it is sufficient to have a λ / 4 plate function (i.e., a π / 2 phase difference function) in the entire visible light range. Specifically, a reverse wavelength dispersion λ / 4 layer is preferable, or it is preferable to combine two or more retardation films with different orientations. For example, a retardation film having a λ / 2 plate function (i.e., a π phase difference function) and a retardation film having a λ / 4 plate function (i.e., a π / 2 phase difference function) may be combined. Furthermore, from the viewpoint of compensating for the anti-reflection function in an oblique direction, it is preferable to further include a layer (positive C plate) having anisotropy in the thickness direction. In particular, when the retarder includes a reverse wavelength dispersion λ / 4 layer and a positive C plate, the effect of the present invention can be obtained more remarkably. In addition, each retardation film may have a tilt orientation or may form a cholesteric orientation state. When the retarder is made of a single layer of retardation film, the above-mentioned tensile stress caused by thermal shrinkage of the polarizer is more likely to concentrate at the ends of the retarder 30 than when it is made of two or more layers. However, according to the present invention, even when the retarder is made of a single layer of retardation film, the in-plane variation in the amount of change in retardation can be effectively suppressed.
[0081] The λ / 4 function over the entire visible light range preferably satisfies the optical characteristics shown in the following formula (1), where Re(λ) is the in-plane retardation value for light with a wavelength of λ nm, and more preferably satisfies the optical characteristics shown in the following formulas (1), (2), and (3). 100nm <Re(550)<160nm (1) (In the formula, Re(550) represents the in-plane phase difference value (in-plane retardation) for light with a wavelength of 550 nm.) Re(450) / Re(550)≦1.0 (2) 1.00≦Re(650) / Re(550) (3) (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.)
[0082] When the "Re(450) / Re(550)" of the retardation film exceeds 1.0, the light leakage on the short wavelength side of the optical laminate including the retardation film becomes large. The value of "Re(450) / Re(550)" is preferably 0.7 or more and 1.0 or less, more preferably 0.80 or more and 0.95 or less, even more preferably 0.80 or more and 0.92 or less, and particularly preferably 0.82 or more and 0.88 or less. The value of "Re(450) / Re(550)" can be arbitrarily adjusted by adjusting the mixing ratio of the polymerizable liquid crystal compound, the lamination angle of the multiple retardation films, and the retardation value.
[0083] The in-plane retardation value of the retardation film can be adjusted by the thickness of the retardation film. Since the in-plane retardation value is determined by the following formula (4), a desired in-plane retardation value (Re(λ)) can be obtained by adjusting Δn(λ) and the thickness d. The thickness of the retardation film is preferably 0.5 μm to 5 μm, more preferably 1 μm to 3 μm. The thickness of the retardation film can be measured by an interference thickness meter, a laser microscope, or a stylus thickness meter. Δn(λ) depends on the molecular structure of the polymerizable liquid crystal compound described later. Re(λ)=d×Δn(λ) (4) (In the formula, Re(λ) represents an in-plane retardation value at a wavelength of λ nm, d represents a thickness, and Δn(λ) represents a birefringence at a wavelength of λ nm.)
[0084] There are no particular limitations on the positive C plate as long as it has anisotropy in the thickness direction. When the liquid crystal is not tilted or cholesteric oriented, it has the optical property expressed by formula (5). nx≒ny <nz (5)
[0085] The in-plane retardation value Re(550) of the positive C plate at a wavelength of 550 nm is usually in the range of 0 to 10 nm, preferably in the range of 0 to 5 nm. The retardation value Rth(550) in the thickness direction at a wavelength of 550 nm is usually in the range of -170 nm or more and -10 nm or less, preferably in the range of -150 nm or more and -20 nm or less, more preferably in the range of -100 nm or more and -40 nm or less. If the retardation value in the thickness direction is in this range, the anti-reflection property from an oblique direction can be further improved.
[0086] The polymerizable liquid crystal compound contained in the retardation film forming composition means a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group, and as the polymerizable liquid crystal compound, a conventionally known polymerizable liquid crystal compound can be used. The photopolymerizable group means a group that can participate in a polymerization reaction by a reactive species generated from a photopolymerization initiator, such as an active radical or an acid. Examples of the photopolymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. In addition, the phase order structure in the thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal. The polymerizable liquid crystal compound may be either rod-shaped or discotic. The polymerizable liquid crystal compound may be used alone or in combination of two or more kinds.
[0087] As the polymerizable liquid crystal compound, from the viewpoint of expressing reverse wavelength dispersion, a liquid crystal having a T-shaped or H-shaped mesogen structure further having birefringence in a direction perpendicular to the molecular long axis direction is preferable, and from the viewpoint of obtaining stronger dispersion, a T-shaped liquid crystal is more preferable. Specific examples of the structure of the T-shaped liquid crystal include those represented by the following formula (I): [ka] Examples of the compound include compounds represented by the following formula:
[0088] In formula (I), Ar represents a divalent aromatic group which may have a substituent. The divalent aromatic group preferably contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a divalent bonding group such as a single bond, -CO-O-, or -O-. G 1 and G 2 each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. L 1 , L 2 , B 1 and B. 2 each independently represents a single bond or a divalent linking group. k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1≦k+l. Here, when 2≦k+l, B 1 and B. 2 , G 1 and G 2 may be the same as or different from each other. E 1 and E 2 each independently represents an alkanediyl group having 1 to 17 carbon atoms, in which a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH2- contained in the alkanediyl group may be substituted with -O-, -S-, or -COO-, and when there are a plurality of -O-, -S-, or -COO-, they are not adjacent to each other. 1 and P 2 each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0089] G 1 and G 2 are each independently preferably a 1,4-phenylenediyl group optionally substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group optionally substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group. In addition, there are multiple G 1 and G 2 At least one of L is preferably a divalent alicyclic hydrocarbon group. 1 Or L 2 G binds to 1 and G 2 It is more preferable that at least one of the groups is a divalent alicyclic hydrocarbon group.
[0090] L 1 and L 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 OCOR a6 -, R a7 OC=OOR a8 -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 are each independently preferably a single bond, -OR a2-1-, -CH2-, -CH2CH2-, -COOR a4-1 - or OCOR a6-1 -, where R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.
[0091] B 1 and B. 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 O.C.O.R. a14 - or R a15 OC=OOR a16 -, where R a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B. 2 are each independently preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 - or OCOR a14-1 -, where R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. B 1 and B. 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.
[0092] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≦k+l≦6, preferably k+l=4, and more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is preferable.
[0093] E 1 and E 2 are each independently preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.
[0094] P 1 Or P 2 Examples of the polymerizable group represented by the formula (I) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Of these, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferable, and an acryloyloxy group is more preferable.
[0095] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocycle which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among them, it is preferable that Ar has a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable that Ar has a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferable that the nitrogen atom has a π electron.
[0096] In formula (I), the total number of π electrons contained in the divalent aromatic group represented by Ar is N πis preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0097] Suitable examples of the aromatic group represented by Ar include the following groups:
[0098] [ka]
[0099] In formulae (Ar-1) to (Ar-23), * represents a linking portion, Z 0 , Z 1 and Z 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.
[0100] Q 1 , Q 2 and Q 3 are each independently -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ represents -, -CO- or O-; R 2’ and R 3’ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0101] J 1 , and J 2 each independently represents a carbon atom or a nitrogen atom.
[0102] Y 1 , Y2 and Y 3 each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.
[0103] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.
[0104] Y 1 , Y 2 and Y 3 Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.
[0105] Y 1 , Y 2 and Y 3 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.
[0106] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is more preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group; Z 1 and Z 2is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group.
[0107] Q 1 , Q 2 and Q 3 -NH-, -S-, -NR 2’ -, -O- are preferred, R 2’ is preferably a hydrogen atom, and among these, -S-, -O-, and -NH- are particularly preferable.
[0108] Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability. In formulas (Ar-16) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, etc.
[0109] Among the polymerizable liquid crystal compounds, compounds having a maximum absorption wavelength of 300 to 400 nm are preferred. When the polymerizable liquid crystal composition contains a photopolymerization initiator, the polymerization reaction and gelation of the polymerizable liquid crystal compound may proceed during long-term storage. However, if the polymerizable liquid crystal compound has a maximum absorption wavelength of 300 to 400 nm, even if the polymerizable liquid crystal composition is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species can be effectively suppressed. Therefore, it is advantageous in terms of long-term stability of the polymerizable liquid crystal composition, and the alignment property and thickness uniformity of the obtained retardation film can be improved. The maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using a UV-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and examples thereof include chloroform and the like.
[0110] An example of the discotic polymerizable liquid crystal compound is a compound containing a group represented by formula (W) (hereinafter, also referred to as "polymerizable liquid crystal compound (W)"). [ka] [In formula (W), R 40 represents the following formulas (W-1) to (W-5). [ka] [In formulas (W-1) to (W-5), X 40 and Z 40 each independently represents an alkanediyl group having 1 to 12 carbon atoms, a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced with -O- or -CO-. m2 represents an integer.
[0111] Examples of the rod-shaped polymerizable liquid crystal compound include compounds represented by formula (II), formula (III), formula (IV), formula (V), formula (VI) and formula (VII). P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (II) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (III) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (IV) P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (V) P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (VI) P11-B11-E11-B12-A11-B13-A12-F11 (VII) [In formulas (II) to (VII), A11 to A14 each independently represent a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. A hydrogen atom contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group, or a nitro group, and a hydrogen atom contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted with a fluorine atom. B11 and B17 each independently represent -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, or -CO-NR 16 -, -NR 16 R represents -CO-, -CO-, -CS-, or a single bond. 16 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. B12 to B16 each independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -, -NR16 It represents -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or a single bond. E11 and E12 each independently represent an alkanediyl group having 1 to 12 carbon atoms, and a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced with -O- or -CO-. F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxy group, a methylol group, a formyl group, a sulfo group (-SO3H), a carboxy group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, and -CH2- constituting the alkyl group and the alkoxy group may be replaced by -O-. P11 and P12 each independently represent a polymerizable group.]
[0112] The content of the polymerizable liquid crystal compound in the retardation film forming composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, based on 100 parts by mass of the solid content of the retardation film forming composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the alignment of the obtained retardation film. In this specification, the solid content of the polymerizable liquid crystal composition means all components excluding volatile components such as organic solvents from the polymerizable liquid crystal composition.
[0113] (5-2) Composition for forming retardation film As described above, the retardation film forming composition contains a polymerizable liquid crystal compound. The retardation film forming composition may further contain reactive additives such as a solvent, a leveling agent, a polymerization initiator, a photosensitizer, a polymerization inhibitor, a crosslinking agent, and an adhesive agent, and it is preferable to contain a solvent and a leveling agent from the viewpoint of processability.
[0114] The retardation film forming composition may contain a solvent. Generally, the polymerizable liquid crystal compound has a high viscosity, so that the retardation film forming composition dissolved in a solvent is easy to apply, and as a result, the retardation film is often easy to form. The solvent is preferably one that can completely dissolve the polymerizable liquid crystal compound, and is preferably a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound.
[0115] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; Examples of suitable solvents include ester solvents such as butyl, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, and nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolidinone. These solvents may be used alone or in combination of two or more.
[0116] The content of the solvent is preferably 50 to 98% by mass based on the total amount of the composition for forming a retardation film. In other words, the content of the solid content in the composition for forming a retardation film is preferably 2 to 50% by mass, more preferably 5 to 30% by mass. When the content of the solid content is 50% by mass or less, the viscosity of the composition for forming a retardation film is low, and the thickness of the retardation film becomes approximately uniform, so that the retardation film tends to be less prone to unevenness. In addition, the content of the solid content can be determined in consideration of the thickness of the retardation film to be produced.
[0117] The retardation film forming composition may contain a leveling agent. The leveling agent is an additive that adjusts the fluidity of the composition and makes the film obtained by applying the composition flatter, and examples of the leveling agent include organic modified silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents. Among them, when horizontal alignment is performed, polyacrylate-based and perfluoroalkyl-based leveling agents are preferred, and when vertical alignment is performed, organic modified silicone-based and perfluoroalkyl-based leveling agents are preferred.
[0118] When the composition for forming a retardation film contains a leveling agent, the content is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily aligned horizontally, and the obtained retardation film tends to be smoother. When the content of the leveling agent relative to the polymerizable liquid crystal compound exceeds the above range, the obtained retardation film tends to be easily uneven. The composition for forming a retardation film may contain two or more kinds of leveling agents.
[0119] The retardation film-forming composition may contain a polymerization initiator. The polymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals by the action of light is preferable from the viewpoint of not depending on the phase state of the thermotropic liquid crystal.
[0120] The photopolymerization initiator can be any known photopolymerization initiator as long as it is a compound capable of initiating the polymerization reaction of the polymerizable liquid crystal compound.Specific examples of the photopolymerization initiator include photopolymerization initiators capable of generating active radicals or acids by the action of light, and among these, photopolymerization initiators that generate radicals by the action of light are preferred.The photopolymerization initiators can be used alone or in combination of two or more kinds.
[0121] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates an active radical, a self-cleavage type benzoin compound, acetophenone compound, hydroxyacetophenone compound, α-aminoacetophenone compound, oxime ester compound, acylphosphine oxide compound, azo compound, etc. can be used. A hydrogen abstraction type benzophenone compound, alkylphenone compound, benzoin ether compound, benzyl ketal compound, dibenzosuberone compound, anthraquinone compound, etc. can be used. Quinone compounds, xanthone compounds, thioxanthone compounds, halogenoacetophenone compounds, dialkoxyacetophenone compounds, halogenobisimidazole compounds, halogenotriazine compounds, triazine compounds, etc. can be used. Iodonium salts and sulfonium salts can be used as photopolymerization initiators that generate acid. Self-cleavage type photopolymerization initiators are preferred from the viewpoint of excellent reaction efficiency at low temperatures, and acetophenone compounds, hydroxyacetophenone compounds, α-aminoacetophenone compounds, and oxime ester compounds are particularly preferred.
[0122] The content of the polymerization initiator in the retardation film-forming composition can be appropriately adjusted depending on the type and amount of the polymerizable liquid crystal compound, but is usually 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the alignment of the polymerizable liquid crystal compound.
[0123] The retardation film forming composition may contain a sensitizer. The sensitizer is preferably a photosensitizer. Examples of the sensitizer include xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.); anthracene compounds such as anthracene and an alkoxy group-containing anthracene (e.g., dibutoxyanthracene, etc.); phenothiazine, rubrene, etc.
[0124] When the retardation film-forming composition contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the retardation film-forming composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0125] In order to stably proceed with the polymerization reaction, the retardation film-forming composition may contain an antioxidant, which can control the degree of progress of the polymerization reaction of the polymerizable liquid crystal compound.
[0126] The antioxidant may be, for example, a primary antioxidant selected from a phenol-based antioxidant, an amine-based antioxidant, a quinone-based antioxidant, or a nitroso-based antioxidant, or a secondary antioxidant selected from a phosphorus-based antioxidant and a sulfur-based antioxidant.
[0127] When the retardation film forming composition contains an antioxidant, the content of the antioxidant is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. The antioxidants can be used alone or in combination of two or more kinds. When the content of the antioxidant is within the above range, polymerization can be performed without disturbing the alignment of the polymerizable liquid crystal compound.
[0128] The retardation film forming composition may contain a reactive additive. The reactive additive preferably has a carbon-carbon unsaturated bond, an active hydrogen reactive group, or a thiol group in its molecule. The "active hydrogen reactive group" here means a group reactive to a group having active hydrogen such as a carboxyl group (-COOH), a hydroxyl group (-OH), or an amino group (-NH2), and representative examples thereof include a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group. The number of reactive groups possessed by the reactive additive is usually 1 to 20, and preferably 1 to 10.
[0129] (5-3) Base material The above-mentioned substrate for forming the retardation film includes glass substrate and film substrate, and film substrate is preferred, and long roll-shaped film is more preferred in terms of continuous production.The resin constituting the film substrate includes, for example, linear polyolefin such as polyethylene and polypropylene; cyclic olefin resin; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid ester; polyacrylic acid ester; cellulose ester such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene oxide; and the like.Among them, from the viewpoint of transparency when used for optical film applications, a film substrate selected from any of triacetyl cellulose, cyclic olefin resin, polymethacrylic acid ester, and polyethylene terephthalate is more preferred.
[0130] Examples of commercially available cellulose ester substrates include "FUJITAC FILM" (manufactured by Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (all manufactured by Konica Minolta Opto, Inc.). Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona, Germany), "Arton" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (all manufactured by Zeon Corporation), and "Apel" (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be formed into a film by known means such as a solvent casting method or a melt extrusion method to form a substrate. Commercially available cyclic olefin resin substrates can also be used. Examples of commercially available cyclic olefin resin substrates include "S-Cina" (registered trademark), "SCA40" (registered trademark) (all manufactured by Sekisui Chemical Co., Ltd.), "ZEONOR Film" (registered trademark) (manufactured by Optes Co., Ltd.), and "Arton Film" (registered trademark) (manufactured by JSR Corporation).
[0131] The thickness of the substrate is preferably thin enough to be practically handled, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the substrate is usually 5 μm to 300 μm, preferably 10 μm to 200 μm, and more preferably 10 to 50 μm. In addition, by peeling off the substrate and transferring the retardation film, a further thinning effect can be obtained.
[0132] (5-4) Alignment film In this specification, the alignment film has an alignment regulating force for aligning a polymerizable liquid crystal compound in a desired direction.
[0133] The alignment film facilitates the liquid crystal alignment of the polymerizable liquid crystal compound. The state of liquid crystal alignment, such as horizontal alignment, vertical alignment, hybrid alignment, and tilt alignment, varies depending on the properties of the alignment film and the polymerizable liquid crystal compound, and the combination can be selected arbitrarily. For example, if the alignment film is a material that exerts horizontal alignment as an alignment control force, the polymerizable liquid crystal compound can form a horizontal alignment or a hybrid alignment, and if the alignment film is a material that exerts vertical alignment, the polymerizable liquid crystal compound can form a vertical alignment or a tilt alignment. The expressions horizontal, vertical, and the like refer to the direction of the optical axis of the aligned polymerizable liquid crystal compound when the retardation film plane is used as a reference. For example, vertical alignment means that the optical axis of the aligned polymerizable liquid crystal compound is in a direction perpendicular to the retardation film plane. The term "vertical" here means 90°±20° relative to the retardation film plane.
[0134] When the alignment film is made of an alignment polymer, the alignment regulating force can be arbitrarily adjusted by the surface state or rubbing conditions, and when it is made of a photoalignment polymer, the alignment regulating force can be arbitrarily adjusted by the polarized light irradiation conditions, etc. In addition, the liquid crystal alignment can be controlled by selecting the physical properties, such as the surface tension and liquid crystallinity, of the polymerizable liquid crystal compound.
[0135] The alignment film formed between the substrate and the retardation film is preferably insoluble in the solvent used when forming the retardation film on the alignment film, and is heat-resistant in the heat treatment for removing the solvent and for aligning the liquid crystal. The alignment film may be an alignment film made of an orienting polymer, a photoalignment film, a groove alignment film, or a stretched film stretched in the alignment direction. When applied to a long rolled film, a photoalignment film is preferred because the alignment direction can be easily controlled.
[0136] The thickness of the alignment film is usually in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 to 300 nm.
[0137] Examples of the alignment polymer used in the rubbed alignment film include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and their hydrolyzates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. These alignment polymers may be used alone or in combination of two or more.
[0138] An example of a rubbing method is to bring an oriented polymer film formed on the surface of a substrate by applying an oriented polymer composition to the substrate and annealing the composition into contact with a rotating rubbing roll wrapped with a rubbing cloth.
[0139] The photo-alignment film is made of a polymer, oligomer, or monomer having a photoreactive group. The photo-alignment film can obtain an alignment control force by irradiating it with polarized light. The photo-alignment film is more preferable in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0140] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it is a group that generates a photoreaction that is the origin of liquid crystal alignment ability, such as molecular alignment induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which occurs by irradiation with light. Among the photoreactive groups, those that cause a dimerization reaction or a photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group that can generate the above-mentioned reaction, those having an unsaturated bond, particularly a double bond, are preferred, and groups having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) are more preferred.
[0141] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. From the viewpoint of easy control of reactivity and expression of alignment control force during photoalignment, chalcone groups and cinnamoyl groups are preferred. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, and formazan groups, and groups having azoxybenzene as a basic structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0142] The polarized light may be irradiated directly from the film surface, or from the substrate side and then transmitted. The polarized light is preferably substantially parallel. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferred. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferred. These lamps are preferred because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. Polarized light can be irradiated by irradiating the light from the light source through an appropriate polarizer. As such a polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0143] (6)Adhesive layer The first adhesive layer 41 is a layer provided as necessary for bonding the first protective layer 10 and the polarizer 5. The second adhesive layer 42 is a layer provided as necessary for bonding the polarizer 5 and the second protective layer 20. The optical laminate preferably includes the first adhesive layer 41 and the second adhesive layer 42. The third adhesive layer 43 is a layer provided for bonding the second protective layer 20 and the retarder 30. The optical laminate preferably includes the third adhesive layer 43.
[0144] The first adhesive layer 41, the second adhesive layer 42, and the third adhesive layer 43 may each be a pressure-sensitive adhesive layer or an adhesive layer. The adhesive layer is a layer formed from a pressure-sensitive adhesive composition (pressure-sensitive adhesive composition), and the adhesive layer is a layer formed from an adhesive composition. The first adhesive layer 41 and the second adhesive layer 42 are preferably adhesive layers. The third adhesive layer 43 is preferably a pressure-sensitive adhesive layer.
[0145] (6-1) Adhesive layer Examples of the adhesive composition forming the adhesive layer include an aqueous adhesive composition, and a curable adhesive composition that is cured by heating or irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Examples of the aqueous adhesive composition include a composition in which a polyvinyl alcohol resin or a urethane resin is dissolved in water as the main component, and a composition in which a polyvinyl alcohol resin or a urethane resin is dispersed in water as the main component. The aqueous adhesive composition may further contain a curable component or a crosslinking agent such as a polyaldehyde, a melamine compound, a zirconia compound, a zinc compound, a glyoxal compound, or a water-soluble epoxy resin. Examples of the aqueous adhesive composition include the adhesive composition described in JP 2010-191389 A, the adhesive composition described in JP 2011-107686 A, the composition described in JP 2020-172088 A, and the composition described in JP 2005-208456 A.
[0146] The curable adhesive composition is preferably an active energy ray curable adhesive composition that contains a curable (polymerizable) compound as a main component and is cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive composition include a cationic polymerization type adhesive composition that contains a cationic polymerizable compound as a curable compound, a radical polymerization type adhesive composition that contains a radical polymerizable compound as a curable compound, and a hybrid type adhesive composition that contains both a cationic polymerizable compound and a radical polymerizable compound as a curable compound.
[0147] The cationically polymerizable compound is a compound or oligomer that undergoes a cationic polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays, or when heated. Specific examples of the cationically polymerizable compound include epoxy compounds, oxetane compounds, and vinyl compounds. The epoxy compounds include alicyclic epoxy compounds (epoxy compounds having an epoxide bonded to an alicyclic ring) such as 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate. aromatic epoxy compounds such as diglycidyl ether of bisphenol A (compounds having an aromatic ring and an epoxy group in the molecule); aliphatic epoxy compounds such as 2-ethylhexyl glycidyl ether and 1,4-butanediol diglycidyl ether (compounds having at least one oxirane ring bonded to an aliphatic carbon atom in the molecule).
[0148] Examples of the oxetane compound include compounds having one or more oxetane rings in the molecule, such as 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane.
[0149] The cationic polymerization adhesive composition preferably contains a cationic polymerization initiator. The cationic polymerization initiator may be a thermal cationic polymerization initiator or a photo-induced cationic polymerization initiator. Examples of the cationic polymerization initiator include aromatic diazonium salts such as benzenediazonium hexafluoroantimonate; aromatic iodonium salts such as diphenyliodonium tetrakis(pentafluorophenyl)borate; aromatic sulfonium salts such as triphenylsulfonium hexafluorophosphate; and iron-arene complexes such as xylene-cyclopentadienyl iron(II) hexafluoroantimonate. The content of the cationic polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the cationic polymerizable compound. Two or more kinds of cationic polymerization initiators may be included.
[0150] Examples of cationic polymerization adhesive compositions include the cationic polymerizable compositions described in JP 2016-126345 A, WO 2019 / 10315 A, and JP 2021-113969 A.
[0151] The radical polymerizable compound is a compound or oligomer that undergoes a radical polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays or when heated, and specifically includes a compound having an ethylenically unsaturated bond. Examples of the compound having an ethylenically unsaturated bond include a (meth)acrylic compound having one or more (meth)acryloyl groups in the molecule, and a vinyl compound having one or more vinyl groups in the molecule.
[0152] Examples of the (meth)acrylic compound include (meth)acrylate monomers having at least one (meth)acryloyloxy group in the molecule, (meth)acrylamide monomers, and (meth)acryl group-containing compounds obtained by reacting two or more functional group-containing compounds and having at least two (meth)acryloyl groups in the molecule, such as (meth)acrylic oligomers.
[0153] The radical polymerization adhesive composition preferably contains a radical polymerization initiator. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator. Examples of the radical polymerization initiator include acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; xanthone, fluorenone, and the like. The content of the radical polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound. Two or more types of radical polymerization initiators may be included.
[0154] Examples of radical polymerization adhesive compositions include the radical polymerizable compositions described in JP 2016-126345 A, JP 2016-153474 A, and WO 2017 / 183335 A.
[0155] The active energy ray-curable adhesive composition may contain additives such as an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow adjuster, a plasticizer, an antifoaming agent, an antistatic agent, a leveling agent, and a solvent, as necessary.
[0156] The bonding of two layers with an adhesive layer can be carried out by coating at least one of the bonding surfaces of each of the two layers with an adhesive composition, overlapping the two layers with the coating layer of the adhesive composition therebetween, pressing the layers together from above and below using a lamination roll or the like, and then drying the adhesive layer, curing it by irradiating it with active energy rays, or curing it by heating.
[0157] Before forming the coating layer of the adhesive layer, at least one of the bonding surfaces of the two layers may be subjected to an adhesion enhancing treatment such as saponification treatment, corona treatment, plasma treatment, primer treatment, anchor coating treatment, etc. To form a coating layer of the adhesive composition, various coating methods can be used, such as a die coater, a comma coater, a gravure coater, a wire bar coater, or a doctor blade coater.
[0158] The light irradiation intensity when irradiating with active energy rays is determined depending on the composition of the active energy ray-curable adhesive composition and is not particularly limited, but is preferably 10 mW / cm 2 More than 1,000mW / cm 2 The irradiation intensity is preferably an intensity in a wavelength region effective for activating a photocationic polymerization initiator or a photoradical polymerization initiator. Irradiation is performed once or multiple times with such a light irradiation intensity, and the integrated light amount is 10 mJ / cm or less. 2 More preferably, it is 100 mJ / cm or more. 2 More than 1,000mJ / cm 2 It is more preferable to set it as follows:
[0159] The light source used to polymerize and cure the active energy ray-curable adhesive composition is not particularly limited, but examples include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black light lamps, microwave excited mercury lamps, and metal halide lamps.
[0160] The thickness of the adhesive layer formed from the aqueous adhesive composition may be, for example, 5 μm or less, preferably 1 μm or less, and more preferably 0.5 μm or less, and may be 0.01 μm or more, and preferably 0.05 μm or more. The thickness of the adhesive layer formed from the active energy ray-curable adhesive composition may be, for example, 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less, and may be 0.1 μm or more, preferably 0.5 μm or more, and more preferably 1 μm or more.
[0161] (6-2) Adhesive layer As the adhesive composition forming the adhesive layer, a conventionally known adhesive composition having excellent optical transparency can be used without any particular limitation, and for example, an adhesive composition having a base polymer such as a (meth)acrylic resin, a urethane resin, a silicone resin, or a polyvinyl ether resin can be used. In addition, an active energy ray curable adhesive composition, a heat curable adhesive composition, etc. may be used. Among these, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, adhesive strength, removability, weather resistance, heat resistance, etc., is preferable. The pressure-sensitive adhesive composition may further contain a crosslinking agent, a silane compound, an antistatic agent, and the like.
[0162] [(Meth)acrylic resin] The (meth)acrylic resin contained in the pressure-sensitive adhesive composition is a structural unit derived from a (meth)acrylic acid alkyl ester represented by the following formula (VIII) (hereinafter, “structural unit (VIII) "). It is preferable that the (meth)acrylic resin be a polymer having (meth)acrylic acid ester polymer as a main component (for example, containing 50 parts by mass or more per 100 parts by mass of the structural unit of the (meth)acrylic resin). [ka] [In formula (VIII), R 10 represents a hydrogen atom or a methyl group, R 20 represents an alkyl group having 1 to 20 carbon atoms, the alkyl group may have any of a linear, branched, or cyclic structure, and a hydrogen atom of the alkyl group may be substituted with an alkoxy group having 1 to 10 carbon atoms.]
[0163] Examples of the (meth)acrylic acid ester represented by formula (VIII) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, i-hexyl (meth)acrylate, n-heptyl (meth)acrylate, Examples of the alkoxy group-containing alkyl acrylate include 2-methoxyethyl (meth)acrylate and ethoxymethyl (meth)acrylate. Among them, it is preferable to include n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, n- and i-nonyl (meth)acrylate, n-decyl (meth)acrylate, i-decyl (meth)acrylate, n-dodecyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, stearyl (meth)acrylate, and t-butyl (meth)acrylate. Examples of the alkoxy group-containing alkyl acrylate include 2-methoxyethyl (meth)acrylate and ethoxymethyl (meth)acrylate. Among them, it is preferable to include n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, and it is particularly preferable to include n-butyl (meth)acrylate.
[0164] The (meth)acrylic acid ester polymer may contain a structural unit derived from another monomer other than the structural unit (VIII). The structural unit derived from the other monomer may be one type or two or more types. Examples of the other monomer that the (meth)acrylic acid ester polymer may contain include a monomer having a polar functional group, a monomer having an aromatic group, and a (meth)acrylamide monomer.
[0165] The monomer having a polar functional group may be a (meth)acrylate having a polar functional group, such as a hydroxy group, a carboxy group, an amino group substituted with an alkyl group having 1 to 6 carbon atoms or an unsubstituted amino group, or a heterocyclic group such as an epoxy group.
[0166] The content of the structural units derived from monomers having a polar functional group in the (meth)acrylic acid ester polymer is preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, even more preferably 0.5 parts by mass or more and 5 parts by mass or less, and particularly preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylic acid ester polymer.
[0167] Examples of the monomer having an aromatic group include (meth)acrylic acid esters having one (meth)acryloyl group and one or more aromatic rings (e.g., benzene ring, naphthalene ring, etc.) in the molecule and having a phenyl group, a phenoxyethyl group, or a benzyl group. By including such a structural unit, it is possible to suppress the phenomenon of white spots occurring in a polarizing plate in a high-temperature and high-humidity environment.
[0168] The content of the structural units derived from the monomer having an aromatic group in the (meth)acrylic acid ester polymer is preferably 20 parts by mass or less, more preferably 4 parts by mass or more and 20 parts by mass or less, and even more preferably 4 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylic acid ester polymer.
[0169] Examples of (meth)acrylamide monomers include N-(methoxymethyl)(meth)acrylamide, N-(ethoxymethyl)(meth)acrylamide, N-(propoxymethyl)(meth)acrylamide, N-(butoxymethyl)(meth)acrylamide, N-(2-methylpropoxymethyl)(meth)acrylamide, etc. By including these structural units, it is possible to suppress the bleeding out of additives such as antistatic agents, which will be described later.
[0170] Furthermore, as a structural unit derived from a monomer other than the structural unit (VIII), a structural unit derived from a styrene-based monomer, a structural unit derived from a vinyl-based monomer, a structural unit derived from a monomer having multiple (meth)acryloyl groups in the molecule, and the like may be included.
[0171] The weight average molecular weight (hereinafter, simply referred to as "Mw") of the (meth)acrylic resin is preferably 500,000 to 2,500,000. When the weight average molecular weight is 500,000 or more, the durability of the adhesive layer in a high temperature and high humidity environment can be improved. When the weight average molecular weight is 2,500,000 or less, the operability during application of a coating liquid containing the adhesive composition is improved. The molecular weight distribution (Mw / Mn), which is expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter, simply referred to as "Mn"), is usually 2 to 10. In this specification, the "weight average molecular weight" and the "number average molecular weight" are polystyrene-equivalent values measured by gel permeation chromatography (GPC).
[0172] When the (meth)acrylic resin is dissolved in ethyl acetate to prepare a solution having a concentration of 20% by mass, the viscosity at 25°C is preferably 20 Pa·s or less, and more preferably 0.1 to 15 Pa·s. When the viscosity of the (meth)acrylic resin at 25°C is within the above range, it contributes to improved durability and reworkability of the optical laminate including the pressure-sensitive adhesive layer formed from the resin. The viscosity can be measured by a Brookfield viscometer.
[0173] The glass transition temperature (Tg) of the (meth)acrylic resin is, for example, −60 to 20° C., preferably −50 to 15° C., more preferably −45 to 10° C., and further preferably −40 to 0° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC).
[0174] The (meth)acrylic resin may contain two or more kinds of (meth)acrylic acid ester polymers. Examples of such (meth)acrylic acid ester polymers include those having a weight average molecular weight smaller than that of the above-mentioned (meth)acrylic acid ester polymer having a weight average molecular weight of 500,000 to 2,500,000, and more specifically, those having a relatively low molecular weight (meth)acrylic acid ester polymer having a weight average molecular weight in the range of 50,000 to 300,000, which is mainly composed of a structural unit (VIII) derived from a (meth)acrylic acid ester.
[0175] The (meth)acrylic resin can be usually produced by a known polymerization method such as a solution polymerization method, a bulk polymerization method, a suspension polymerization method, or an emulsion polymerization method. In the production of the (meth)acrylic resin, the polymerization is usually carried out in the presence of a polymerization initiator. The amount of the polymerization initiator used is usually 0.001 to 5 parts by mass with respect to 100 parts by mass of the total of all the monomers constituting the (meth)acrylic resin. The (meth)acrylic resin can also be produced by a method of polymerization using active energy rays such as ultraviolet rays.
[0176] [Crosslinking agent] The pressure-sensitive adhesive composition preferably contains a crosslinking agent. Examples of the crosslinking agent include conventional crosslinking agents (e.g., isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc.), and from the viewpoints of the pot life of the pressure-sensitive adhesive composition, crosslinking speed, and durability of the optical laminate, it is particularly preferable to use an isocyanate compound.
[0177] The isocyanate compound is a compound having at least two isocyanato groups (-NCO) in the molecule. Specific examples include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane, and dimers and trimers of these isocyanate compounds are also included. Two or more types of isocyanate compounds may be combined.
[0178] The proportion of the crosslinking agent is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic resin.
[0179] [Silane compounds] The pressure-sensitive adhesive composition may further contain a silane compound. Examples of the silane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane. The silane compound may also contain an oligomer derived from the above silane compound.
[0180] The content of the silane compound in the pressure-sensitive adhesive composition is usually 0.01 to 10 parts by mass, and preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. When the content of the silane compound is 0.01 part by mass or more, the adhesion between the pressure-sensitive adhesive layer and the adherend tends to be improved, and when the content is 10 parts by mass or less, bleeding out of the silane compound from the pressure-sensitive adhesive layer tends to be suppressed.
[0181] [Antistatic agent] The pressure-sensitive adhesive composition may further contain an antistatic agent. Examples of the antistatic agent include known ones, and ionic antistatic agents are preferred. Examples of the cationic component constituting the ionic antistatic agent include organic cations and inorganic cations. Examples of the organic cation include pyridinium cation, imidazolium cation, ammonium cation, sulfonium cation, phosphonium cation, etc. Examples of the inorganic cation include alkali metal cations such as lithium cation, potassium cation, sodium cation, and cesium cation, and alkaline earth metal cations such as magnesium cation and calcium cation. Examples of the anionic component constituting the ionic antistatic agent include inorganic anions and organic anions, but an anionic component containing a fluorine atom is preferred in terms of excellent antistatic performance. Examples of the anionic component containing a fluorine atom include hexafluorophosphate anion (PF6 - ), bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - ], bis(fluorosulfonyl)imide anion [(FSO2)2N - ] anion, tetrakispentafluorophenylborate anion [(CF 5) 4B - ] etc. In view of excellent stability over time of the antistatic performance of the pressure-sensitive adhesive composition, an ionic antistatic agent that is solid at room temperature is preferred. The content of the antistatic agent is, for example, 0.01 to 20 parts by mass, preferably 0.1 to 10 parts by mass, and more preferably 1 to 7 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin.
[0182] The adhesive composition may contain one or more additives such as an ultraviolet absorber, a solvent, a crosslinking catalyst, a tackifier resin, a plasticizer, etc. It is also useful to blend an ultraviolet curable compound into the adhesive composition, form an adhesive layer, and then irradiate the adhesive with ultraviolet light to cure the adhesive layer, thereby forming a harder adhesive layer.
[0183] The adhesive layer can be formed, for example, by dissolving or dispersing the adhesive composition in a solvent to prepare a solvent-containing adhesive composition, which is then applied to the surface of a substrate or a layer on which the adhesive layer is to be formed, and drying.
[0184] The thickness of the pressure-sensitive adhesive layer is usually 0.1 to 30 μm, preferably 3 to 30 μm, and more preferably 5 to 25 μm.
[0185] (7) Adhesive layer The optical laminate can include a pressure-sensitive adhesive layer 50 laminated on the side of the phase shifter 30 opposite to the second protective layer 20. For the pressure-sensitive adhesive layer 50, the description of the above (6-2) Pressure-sensitive adhesive layer is cited.
[0186] From the viewpoint of suppressing the in-plane variation of the retardation change amount, the storage modulus G' of the pressure-sensitive adhesive layer 50 at a temperature of 85°C is preferably 0.005 MPa or more, more preferably 0.01 MPa or more, and even more preferably 0.015 MPa or more. The storage modulus G' is usually 0.1 MPa or less, and may be 0.08 MPa or less. The storage modulus G' can be measured according to the description in the [Examples] section.
[0187] The thickness of the pressure-sensitive adhesive layer 50 is usually 5 μm or more, and preferably 10 μm or more. The thickness of the pressure-sensitive adhesive layer 50 is usually 35 μm or less, and preferably 30 μm or less.
[0188] (8) Laminate α In the case where the optical laminate includes the pressure-sensitive adhesive layer 50, a laminate from a layer adjacent to the surface of the polarizer 5 facing the retarder 30 to a layer adjacent to the surface of the pressure-sensitive adhesive layer 50 facing the retarder 30 is referred to as a "laminate α" in this specification. For example, in the optical laminate shown in FIG. 2, the laminate α is a laminate of the second pressure-sensitive adhesive layer 42, the second protective layer 20, the third pressure-sensitive adhesive layer 43, and the retarder 30. 2, the layer adjacent to the surface of the polarizer 5 facing the phase shifter 30 is the second pressure-sensitive adhesive layer 42. When the polarizer 5 and the second protective layer 20 are in direct contact with each other without the second pressure-sensitive adhesive layer 42, the layer adjacent to the surface of the polarizer 5 facing the phase shifter 30 is the second protective layer 20. In the optical laminate shown in FIG. 2, the layer adjacent to the surface of the pressure-sensitive adhesive layer 50 facing the phase shifter 30 is the phase shifter 30. In the case where the optical laminate has the second adhesive layer 42, when the second adhesive layer 42 is formed from an aqueous adhesive composition, the second adhesive layer 42 is excluded from the laminate α. That is, when the second adhesive layer 42 is formed from an aqueous adhesive composition, the laminate α is a laminate of the second protective layer 20, the third adhesive layer 43, and the retarder 30 in the optical laminate shown in FIG.
[0189] The tensile modulus of laminate α at a temperature of 23°C is E3 [MPa] and its thickness is T3 [μm]. In this case, the laminate α has the following formula (iv): 7000≦E3×T3≦22000 (iv) It is preferable that the following is satisfied.
[0190] When the laminate α satisfies formula (iv), the in-plane variation in the amount of change in retardation and the corrosion of the metal member can be more effectively suppressed. When E3×T3 is 22000 or less, the tensile stress caused by the shrinkage of the polarizer due to heat is not easily transmitted to the retarder 30, so that the in-plane variation in the amount of change in retardation can be suppressed. On the other hand, when E3×T3 is 7000 or more, it is considered that the laminate α contains a layer with low material permeability having a feature such as a high crosslink density. At this time, the dichroic dye such as iodine in the polarizer 5 can be prevented or suppressed from migrating to the metal member due to the diffusion, and the corrosion of the metal member (electrode, etc.) present near the optical laminate in the image display device can be prevented or suppressed.
[0191] From the viewpoint of preventing corrosion of metal members, the value of E3×T3 in formula (iv) is more preferably at least 7500, further preferably at least 8000, still further preferably at least 8500, and particularly preferably at least 10000. From the viewpoint of suppressing in-plane variation in retardation change amount, the value of E3×T3 is more preferably at most 20000, further preferably at most 15000, and particularly preferably at most 12000.
[0192] The tensile modulus E3 of the laminate α at a temperature of 23° C. is usually 1200 MPa or less, preferably 1000 MPa or less, and usually 500 MPa or more, preferably 600 MPa or more. The tensile modulus E3 can be measured according to the description in the [Examples] section.
[0193] <Image display device> The image display device includes the optical laminate according to the present invention and an image display element (such as an organic EL display element). The optical laminate is disposed on the viewing side of the image display element. The optical laminate can be attached to the image display element using the pressure-sensitive adhesive layer 50.
[0194] The image display device is not particularly limited, and examples thereof include image display devices such as organic electroluminescence (organic EL) display devices, inorganic electroluminescence (inorganic EL) display devices, liquid crystal display devices, and electroluminescence display devices.
[0195] The image display device can be used as mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signs, measuring instruments or gauges, office equipment, medical equipment, computing equipment, and the like. EXAMPLES
[0196] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the following, parts and % representing amounts used and contents are based on mass unless otherwise specified.
[0197] <Measurement and Evaluation> (1) Thickness of layer, film, or laminate α Unless otherwise specified, the thickness of the layer, film, or laminate α was measured using a laser microscope ("LEXT" manufactured by Olympus Corporation) or a digital micrometer ("MH-15M" manufactured by Nikon Corporation).
[0198] (2) Tensile modulus E of protective film (85°C) A measurement sample with a long side of 100 mm and a short side of 50 mm was cut out from a single protective film. In accordance with JIS K7161:1994 and JIS K7127:1999, if the measurement sample did not have a yield point, the tensile breaking strain was taken as the breaking elongation, and if it had a yield point, the tensile breaking elongation strain was taken as the breaking elongation, and the breaking elongation was measured. The measurement sample was clamped at both ends in the long side direction with the upper and lower grips of a tensile testing machine (Autograph AG-Xplus test machine manufactured by Shimadzu Corporation) so that the distance between the grips was 5 cm, and the measurement sample was pulled in the long side direction at a pulling speed of 300 mm / min under an environment of a temperature of 85°C and a relative humidity of 55% RH, and the tensile modulus [MPa] in the long side direction at a temperature of 85°C and a relative humidity of 55% RH was calculated.
[0199] (3) In-plane retardation value of layer or film The in-plane retardation value [nm] of the layer or film at a wavelength of 550 nm was measured using a retardation measuring device (KOBRA-WPR, manufactured by Oji Scientific Instruments Co., Ltd.).
[0200] (4) Moisture permeability of protective film The moisture permeability of the second protective layer was measured under the following measurement conditions. Test item: Water vapor permeability Test method: Moisture sensor method Measurement equipment: Lyssy L80 series water vapor transmission meter Sample preparation method: After attaching an aluminum mask to the second protective layer surface of a laminate including a supporting substrate and a second protective layer, which will be described later, the supporting substrate was peeled off, and an aluminum mask was attached to the peeled surface to prepare a measurement sample. For the second protective layers 8 and 9 having supporting substrates on both sides, one supporting substrate was peeled off, an aluminum mask was attached to the peeled surface, and then the other supporting substrate was peeled off, and an aluminum mask was further attached to the peeled surface to prepare a measurement sample. The second protective layers 4 and 5, and the second protective layer 7 (a triacetyl cellulose film having a thickness of 20 μm) used in Comparative Example 1 did not have a supporting substrate, so the operation of peeling off the supporting substrate was not performed. Measurement conditions Measurement temperature: 40℃ Relative humidity: 90%RH Measurement area: 2nd protective layer 1~5: 7.1×10 -4 m 2 (Transmission area when wearing a mask) 2nd protective layer 6~9: 7.9×10 -5 m 2 (Transmission area when wearing a mask) Measurement sample installation direction: Any
[0201] (5) Photoelasticity of protective film The photoelastic modulus was calculated from the slope of the function of stress and phase difference value, which was measured at the center of the sample (23°C / wavelength 550nm) while clamping both ends of the sample (size 1cm x 10cm) and applying stress (0.5N to 3N) using a phase difference measuring device KOBRA-WPR (manufactured by Oji Scientific Instruments Co., Ltd.). Note that the photoelastic modulus does not depend on thickness, so a film of an appropriate thickness was formed for each resin, and the measured value was used for each thickness.
[0202] (6) Boron content of polarizer 0.2 g of the polarizer was dissolved in 200 g of a 1.9% by mass mannitol aqueous solution. The resulting aqueous solution was titrated with a 1 mol / L NaOH aqueous solution, and the boron content [mass %] of the polarizer was calculated by comparing the amount of NaOH solution required for neutralization with the calibration curve.
[0203] (7) Storage modulus G' of adhesive layer (85°C) The storage modulus G' of the adhesive layer was measured using a viscoelasticity measuring device (MCR-301, Anton Paar). The same adhesive layer as used in the examples and comparative examples was cut to a width of 30 mm and a length of 30 mm, the release film was peeled off, and multiple sheets were laminated to a thickness of 200±10 μm, which were then attached to a measurement stage. Measurements were performed in the bonded state in the temperature range of -20°C to 100°C under conditions of a frequency of 1.0 Hz, a deformation of 1%, a normal force of 1 N, and a heating rate of 5°C / min, and the storage modulus G' [MPa] at a temperature of 85°C was obtained.
[0204] (8) Tensile modulus E3 of laminate α (23°C) (8-1) Preparation of laminate α (8-1-1) When the second adhesive layer is formed from a water-based adhesive The surface of the second protective layer and the surface exposed by peeling off the substrate A of the retarder were each subjected to a corona treatment (0.3 kW, treatment speed 3 m / min). The corona-treated surface of the second protective layer and the corona-treated surface of the retarder were bonded together via a third adhesive layer described later, to obtain a laminate α (or laminate α with a supporting substrate) including (supporting substrate) the second protective layer / third adhesive layer / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B / substrate B in this order.
[0205] (8-1-2) When the second adhesive layer is a pressure-sensitive adhesive layer The surface of the second protective layer (the surface opposite to the surface having the support substrate) to which the support substrate was attached via the pressure-sensitive adhesive layer (second pressure-sensitive adhesive layer) and the surface exposed by peeling off the substrate A of the retarder were each subjected to a corona treatment (0.3 kW, treatment speed 3 m / min). The corona-treated surface of the second protective layer and the corona-treated surface of the retarder were attached via a third pressure-sensitive adhesive layer described later to obtain a laminate with a support substrate α including (support substrate) the second pressure-sensitive adhesive layer / second protective layer / pressure-sensitive adhesive layer 1 / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B / substrate B in this order.
[0206] (8-1-3) When the second protective layer is a resin layer The surface of the second protective layer and the surface exposed by peeling off the substrate A of the retarder were each subjected to a corona treatment (0.3 kW, treatment speed 3 m / min). The corona-treated surface of the second protective layer and the corona-treated surface of the retarder were bonded together via a third adhesive layer described later, to obtain a laminate α (or laminate α with a supporting substrate) including (supporting substrate) the second protective layer / third adhesive layer / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B / substrate B in this order.
[0207] In the above (8-1-1) to (8-1-3), when the laminate α is produced using a laminate including a supporting substrate and a second protective layer, the surface of the second protective layer refers to the surface of the second protective layer in the laminate, which will be described later. When the laminate α is produced using a second protective layer having supporting substrates on both sides, the surface of the second protective layer refers to the surface of the second protective layer exposed by peeling off one of the supporting substrates.
[0208] The procedure for producing the laminate α is not limited to the above.
[0209] (8-2) Preparation of measurement sample and measurement of tensile modulus E3 The method of preparing the measurement sample will be described with reference to FIG. 3. The laminate α was cut into a piece of 60 mm×200 mm. A glued mount 17 of 60 mm×200 mm was also prepared. This glued mount 17 had a cutout 18 cut out in a rectangle of 10 mm×140 mm in the center. When the second protective layer had a supporting substrate, the supporting substrate was peeled off and removed from the laminate α, and the laminate was attached to the glued mount so that the surface of the second protective layer (the adhesive layer in the case of (8-1-2) above) was in contact with the glue of the glued mount. Then, the substrate layer B was peeled off. In this way, a sample as shown in FIG. 3 was obtained. The laminate α16 was present in the cutout 18, and the glued mount 17 and the laminate α16 were attached to each other in the other parts. Next, a rectangular portion of 10 mm×60 mm (the portion surrounded by the dotted line in FIG. 3) was cut out so as to include the cutout portion 18 of the adhesive mount 17, and this was used as a sample for measuring the tensile modulus of elasticity.
[0210] The tensile modulus E3 was measured according to JIS K7161. Using a test machine (Shimadzu Corporation Autograph AG-Xplus test machine), the mount parts (shaded parts in Figure 3) on both ends of the above measurement sample were gripped and pulled at a speed of 1 mm / min to calculate the tensile modulus of elasticity [MPa] in the long side direction. The tensile test was carried out in a room environment of 23°C and 50% humidity.
[0211] (9) Evaluation of in-plane variation in retardation change The in-plane variation of the change in the in-plane retardation value when the optical laminate was placed under high temperature (in-plane variation of the retardation change) was measured and evaluated according to the following procedure. A sample of 120 mm x 60 mm with the retarder's slow axis in the long side direction was cut out from the optical laminate. The sample was attached to alkali-free glass (manufactured by Corning, product number: EAGLE XG (registered trademark)) via the adhesive layer of the sample to prepare an evaluation sample. The in-plane retardation value of the evaluation sample at a wavelength of 550 nm was measured using a retardation measuring device (manufactured by Oji Scientific Instruments, KOBRA-WPR). The in-plane retardation value was measured at the in-plane center of the evaluation sample and at the center positions of each of the four edges (total of five points).
[0212] The evaluation sample was placed in an oven, and a heat resistance test was performed by heating the evaluation sample at a temperature of 85°C for 168 hours. The evaluation sample was removed from the oven, and 1.5 hours later, the above-mentioned retardation measuring device was used to measure the in-plane retardation value at the same points as the above-mentioned five points at a wavelength of 550 nm, and the change amount ΔRe of the in-plane retardation value before and after the heat resistance test at the five points was obtained. The change amount of the in-plane retardation value at the in-plane center of the evaluation sample was set to ΔRe1, and the change amount of the in-plane retardation value at each center position of the four end sides was set to ΔRe2 to 5, respectively. From these, the values of |Re1-Re2|, |Re1-Re3|, |Re1-Re4|, and |Re1-Re5| were obtained. The difference X between the maximum value and the minimum value of these values was obtained. Based on the value of the difference X, the in-plane variation of the retardation change amount was evaluated according to the following criteria. Among the following criteria, A+ is the best evaluation and the in-plane variation of the retardation change amount is the smallest. D is the worst evaluation, and has the largest in-plane variation in the amount of phase difference change. A+:X value is less than 1.2 A: The value of X is 1.2 or more and less than 2.0 B: X value is 2.0 or more and less than 2.5 C: X value is 2.5 or more and less than 3.0 D:X value is 3.0 or more
[0213] (10) Evaluation of metal corrosion using optical laminates A metal-layered glass substrate was prepared by laminating a metal aluminum layer and a metal titanium layer in this order on the surface of an alkali-free glass substrate by sputtering. Next, the optical laminate obtained in the examples and comparative examples was cut into a size of 50 mm x 50 mm, and the metal titanium layer side of the metal-layered glass substrate was attached to the adhesive layer of the optical laminate to prepare an evaluation sample. The evaluation sample was stored in an oven at a temperature of 85°C and a relative humidity of 85%RH for 350 hours, and then the evaluation sample was removed from the oven. The evaluation sample was placed on a backlight with the glass substrate facing down, and the number and size of bright spots due to light leakage were observed, and metal corrosion was evaluated according to the following criteria. A+: No bright spots A: 1 to 5 bright spots of 0.1 to 0.5 mm B+: 6 to 15 bright spots of 0.1 to 0.5 mm or less, or 0.5 to 1.0 mm bright spots 5 or less B: 6 to 15 bright spots of 0.5 to 1.0 mm C: More than 15 bright spots are observed over the entire surface, but there are some areas where there are no bright spots. D: More than 15 bright spots are evenly distributed over the entire surface.
[0214] [Preparation of polarizer] (1) Preparation of polarizer 1 A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99.9% or more was uniaxially stretched to a stretching ratio of 4.5 times in a dry state, and while maintaining a tension state, it was immersed for 60 seconds in a dye bath at 28°C containing 0.05 parts of iodine and 5 parts of potassium iodide per 100 parts of water.
[0215] Next, the film was immersed for 110 seconds in a boric acid aqueous solution 1 at 64° C. containing 5.5 parts of boric acid and 15 parts of potassium iodide per 100 parts of water. Next, the film was immersed for 30 seconds in a boric acid aqueous solution 2 at 67° C. containing 2.3 parts of boric acid and 15 parts of potassium iodide per 100 parts of water. Thereafter, the film was washed with pure water at 3° C. and dried to obtain a polarizer 1. The boron content of the polarizer 1 measured by the above method was 2.8% by mass. The thickness of the polarizer was 8 μm.
[0216] (2) Preparation of polarizer 2 Polarizer 2 was produced in the same manner as Polarizer 1, except that the content of boric acid in the boric acid aqueous solution 2 was changed to 5.5 parts. Polarizer 2 had a thickness of 8 μm and a boron content of 4.1 mass %.
[0217] [Protective film production and preparation] (1) Preparation of First Protective Layer 1 A triacetyl cellulose (TAC) film (KC2UATAC manufactured by Konica Minolta, Inc., thickness T1: 25 μm) was prepared as the first protective layer 1. The tensile modulus E1 of the first protective layer 1 at a temperature of 85° C. was 830 MPa.
[0218] (2) Preparation of first protective layer 2 A first protective layer 2 (thickness T1: 32 μm) was obtained by forming a hard coat layer with a thickness of 7 μm on one side of the first protective layer 1. The tensile modulus E1 of the first protective layer 2 at a temperature of 85° C. was 700 MPa.
[0219] (3) Preparation of second protective layer 1 A polyethylene terephthalate film (PET film) having a thickness of 38 μm ("TN100" manufactured by Toyobo Co., Ltd., having a release layer containing a non-silicone release agent) was prepared as a supporting substrate. The following components were mixed to prepare a composition containing a thermoplastic resin. Cyclic polyolefin resin (ZEON Corporation's "ZEONOR ZF14"): 10 parts Cyclohexane: 90 parts
[0220] A composition containing the above thermoplastic resin was applied onto the release layer of the supporting substrate using a die by a backcoat method, and the applied layer was then dried under conditions of 40° C. for 1 minute, 70° C. for 1 minute, and 120° C. for 2 minutes to produce a laminate having a cyclic polyolefin resin layer with a thickness T2 of 2 μm as the second protective layer 1. The second protective layer 1 had a tensile modulus E2 of 450 MPa at a temperature of 85° C., an in-plane retardation value of 0.5 nm at a wavelength of 550 nm, and a moisture permeability of 63 g / m 2 / 24hr, photoelasticity coefficient 3.5×10 -12 Pa -1 It was.
[0221] (4) Preparation of second protective layer 2 A laminate having a cyclic polyolefin resin layer having a thickness T2 of 3 μm was prepared as the second protective layer 2 in the same manner as the preparation of the second protective layer 1, except that the amount of the composition containing a thermoplastic resin applied onto the release layer of the support substrate was changed. The tensile modulus E2 of the second protective layer 2 at a temperature of 85° C. was 450 MPa, and the moisture permeability was 37 g / m 2 / 24hr, photoelasticity coefficient 3.5×10 -12 Pa -1 It was.
[0222] (5) Preparation of second protective layer 3 A laminate having a cyclic polyolefin resin layer having a thickness T2 of 4 μm was prepared as the second protective layer 3 in the same manner as the preparation of the second protective layer 1, except that the amount of the composition containing a thermoplastic resin applied onto the release layer of the support substrate was changed. The tensile modulus E2 of the second protective layer 3 at a temperature of 85° C. was 450 MPa, and the moisture permeability was 19 g / m 2 / 24hr, photoelasticity coefficient 3.5×10 -12 Pa -1 It was.
[0223] (6) Preparation of second protective layer 4 A cyclic polyolefin resin film having a thickness T2 of 13 μm was prepared as the second protective layer 4. The second protective layer 4 had a tensile modulus E2 of 620 MPa at a temperature of 85° C. and a moisture permeability of 4.8 g / m 2 / 24hr, photoelasticity coefficient 3.5×10 -12 Pa -1 It was.
[0224] (7) Preparation of second protective layer 5 A cyclic polyolefin resin film having a thickness T2 of 23 μm was prepared as the second protective layer 5. The second protective layer 5 had a tensile modulus E2 of 620 MPa at a temperature of 85° C. and a moisture permeability of 2.6 g / m 2 / 24hr, photoelasticity coefficient 3.5×10 -12 Pa -1 It was.
[0225] (8) Preparation of second protective layer 6 A 38 μm-thick polyethylene terephthalate film (PET film) ("TN100" manufactured by Toyobo Co., Ltd., having a release layer containing a non-silicone release agent) was prepared as a supporting substrate. In addition, a composition containing a (meth)acrylic resin was prepared by dissolving 10 parts of a 60 μm-thick (meth)acrylic resin film (total light transmittance: 93.5%, Tg: 105° C.) prepared by melt extrusion according to JP 2013-254133 A in 90 parts of toluene.
[0226] On the release layer of the support substrate, after applying the composition containing the above (meth)acrylic resin using a die by the backcoating method, the coating layer was dried under the conditions of 40°C for 1 minute, 70°C for 1 minute, 100°C for 1 minute, and then 130°C for 2 minutes, thereby producing a laminate having a (meth)acrylic resin layer with a thickness T2 of 2 μm as the second protective layer 6. The tensile modulus of elasticity E2 at a temperature of 85°C of the second protective layer 6 was 850 MPa, the in-plane retardation value at a wavelength of 550 nm was 0.1 nm, the moisture permeability was 1100 g / m 2 / 24 hr, and the photoelastic modulus was 0.3×10 -12 Pa -1 It was.
[0227] (9) Preparation of the second protective layer 8 As the support substrate, two annular polyolefin films with a thickness of 50 μm were prepared. Also, the following components were blended to prepare a resin composition. · 4-Hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.): 70 parts · Dipentaerythritol polyacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.): 30 parts · Irgacure 184 (manufactured by Ciba Specialty Chemicals): 3 parts
[0228] The obtained resin composition was coated between the two support substrates using a high-speed laminator. Subsequently, ultraviolet rays were irradiated under the following conditions to produce a laminate having a cured resin layer with a thickness T2 of 1 μm as the second protective layer 8. The tensile modulus of elasticity E2 at a temperature of 85°C of the second protective layer 8 was 850 MPa, the in-plane retardation value at a wavelength of 550 nm was 0.1 nm, the moisture permeability was 2200 g / m 2 / 24 hr, and the photoelastic modulus was 0.3×10 -12 Pa -1 It was. <UV irradiation conditions> GS-UV lamp high-pressure mercury lamp was used · Integrated light quantity of the UV wavelength region UVA was 400 mJ / cm 2 (Measured value by UV Power PuckII manufactured by FusionUV)
[0229] (10) Preparation of the second protective layer 9 Except for the following changes to the resin composition and thickness T2 of 2 μm A laminate having a cured resin layer with a thickness T2 of 2 μm was prepared as the second protective layer 9 in the same manner as the second protective layer 8. The tensile modulus E2 of the second protective layer 9 at a temperature of 85° C. was 850 MPa, the in-plane retardation value at a wavelength of 550 nm was 0.1 nm, and the moisture permeability was 1100 g / m 2 / 24hr, photoelasticity coefficient is 0.3×10 -12 Pa -1 It was. 4-Hydroxybutyl acrylate (Osaka Organic Chemical Industry Co., Ltd.): 30 parts Dipentaerythritol polyacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd.): 70 parts Irgacure 184 (manufactured by Chiba Specialty Chemicals): 3 parts
[0230] [Preparation of active energy ray curable adhesive] (1) Preparation of active energy ray curable adhesive 1 The components listed below were mixed and degassed to prepare an active energy ray-curable adhesive 1. (cationically polymerizable compound) 3',4'-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 70 parts Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts (Photocationic polymerization initiator) Product name: CPI-100 (San-Apro Co., Ltd., 50% propylene carbonate solution): 4.5 parts (actual solid content 2.25 parts) (Photosensitizer assistant) 1,4-diethoxynaphthalene: 2 parts
[0231] (2) Preparation of active energy ray curable adhesive 2 The components listed below were mixed and then degassed to prepare an active energy ray-curable adhesive 2. (cationically polymerizable compound) 3',4'-Epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 32.5 parts 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (trade name: EHPE3150, manufactured by Daicel Corporation): 17.5 parts 3-[(benzyloxy)methyl]-3-ethyloxetane (aromatic-containing oxetane compound, product name: TCM-104, manufactured by TRONLY): 10.0 parts 3-Ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (product name: OXT-221, manufactured by Toagosei Co., Ltd.): 40.0 parts (Photocationic polymerization initiator) Sulfonium-based photopolymerization initiator (product name: CPI-100P, manufactured by San-Apro Co., Ltd., 50% by weight solution): 2.6 parts (actual solid content: 1.3 parts) (Photosensitizer assistant) 1,4-diethoxynaphthalene: 2.0 parts
[0232] [Preparation of adhesive layer] The following acrylic pressure-sensitive adhesive layers 1 and 2 were prepared, both sides of which were bonded to release films. (1) Preparation of adhesive layer 1 (1-1) Preparation of acrylic resin solution 1 Into a reaction vessel equipped with a condenser, a nitrogen inlet tube, a thermometer, and a stirrer, 100 parts of ethyl acetate, A mixed solution of 99.0 parts of butyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, and 0.5 parts of acrylic acid was charged, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 55°C. Then, a solution of 0.12 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54-56°C, and when the concentration of the acrylic resin reached 35% by mass, the addition of ethyl acetate was stopped, and the temperature was kept at this temperature until 6 hours had elapsed from the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the acrylic resin to 20% by mass, and acrylic resin solution 1 was prepared. The obtained acrylic resin had a weight average molecular weight Mw of 1.7 million and a molecular weight distribution Mw / Mn of 3.9. The Mw and Mn were measured in terms of standard polystyrene using two "TSKgel GMHHR-H(S)" columns manufactured by Tosoh Corporation connected in series as columns in a GPC apparatus, tetrahydrofuran as an eluent, a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40° C., and a flow rate of 1 mL / min.
[0233] (1-2) Preparation of Pressure Sensitive Adhesive Composition 1 To 80 parts of the solid content of the acrylic resin solution 1 obtained in (1-1) above, 20 parts (solid content) of a bifunctional acrylate (obtained from Shin-Nakamura Chemical Co., Ltd.; product number "A-DOG"), 2.5 parts of a crosslinking agent (manufactured by Mitsui Chemicals: product name "D-101E" (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration 75 mass%)) based on active ingredients, 1.5 parts of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: product name "Irgacure 500"), and 0.3 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.: product name "KBM-403") were added, and ethyl acetate was further added so that the solid content concentration became 13%, thereby obtaining a pressure-sensitive adhesive composition 1.
[0234] A-DOG is a diacrylate of an acetal compound of hydroxypivalaldehyde and trimethylolpropane, and has the following structure: [Chemical formula]
[0235] (1 - 3) Preparation of the Adhesive Layer 1 The adhesive composition 1 prepared in the above (1 - 2) was applied onto the release-treated surface of a release film made of a polyethylene terephthalate film with release treatment [manufactured by Mitsubishi Chemical Corporation: MRV (V04) (thickness: 38 μm)] using an applicator so that the thickness after drying would be 5 μm, and then dried at 100°C for 1 minute to prepare an adhesive layer (adhesive sheet). Next, the surface of the obtained adhesive layer on the side opposite to the release film side was bonded to the release-treated surface of a release film made of a polyethylene terephthalate film with release treatment [manufactured by Mitsubishi Chemical Corporation: MRF (thickness: 38 μm)]. Subsequently, ultraviolet rays were irradiated under the following conditions to prepare the adhesive layer 1. The storage elastic modulus G' of the adhesive layer 1 at a temperature of 85°C was 0.125 MPa. <UV Irradiation Conditions> · Using a Fusion UV lamp system (manufactured by Fusion UV Systems), type H bulb · Integrated light quantity of the UV wavelength region UVA: 250 mJ / cm 2 (Measuring instrument: Measured value by UV Power PuckII manufactured by FusionUV)
[0236] (2) Preparation of the Adhesive Layer 2 (2 - 1) Preparation of the Acrylic Resin Solution 2 A mixed solution of 81.8 parts of ethyl acetate, 90.0 parts of butyl acrylate, 5.0 parts of methyl acrylate and 5.0 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 55 ° C. Then, a solution of 0.15 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54 to 56 ° C., and the addition of ethyl acetate was stopped when the concentration of the acrylic resin reached 35% by mass, and the temperature was kept at this temperature until 6 hours had passed since the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the acrylic resin to 20% by mass, and acrylic resin solution 2 was prepared. The resulting acrylic resin had a weight average molecular weight Mw of 1.6 million and a molecular weight distribution Mw / Mn of 4.5. Mw and Mn were measured in terms of standard polystyrene using two "TSKgel GMHHR-H(S)" columns manufactured by Tosoh Corporation connected in series as columns in a GPC apparatus, tetrahydrofuran as an eluent, a sample concentration of 2 mg / mL, a sample introduction amount of 100 μL, a temperature of 40° C., and a flow rate of 1 mL / min.
[0237] (2-2) Preparation of Pressure Sensitive Adhesive Composition 2 To 100 parts of the solid content of the acrylic resin solution 2 obtained in (2-1), 0.15 parts on an active ingredient basis of a crosslinker (manufactured by Mitsui Chemicals: product name "D-101E" (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration 75 mass%)) and 0.2 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.: product name "KBM-403") were added, and ethyl acetate was further added to adjust the solid content concentration to 13%, thereby obtaining a pressure-sensitive adhesive composition 2.
[0238] (2-3) Preparation of adhesive layer 2 The adhesive composition 2 prepared in (2-2) above was applied to the release-treated surface of a release film made of a release-treated polyethylene terephthalate film [manufactured by Mitsubishi Chemical: MRV (V04) (thickness: 38 μm)] using an applicator so that the thickness after drying would be 15 μm, and the coating was dried at 100° C. for 1 minute to prepare an adhesive layer (adhesive sheet). Next, the surface of the resulting adhesive layer opposite to the release film side was attached to the release-treated surface of a release film made of a release-treated polyethylene terephthalate film [manufactured by Mitsubishi Chemical: MRF (thickness: 38 μm)] to prepare an adhesive layer 2. The storage modulus G' of the adhesive layer 2 at a temperature of 85° C. was 0.0255 MPa.
[0239] [Fabrication of phase shifter 1] (1) Preparation of retardation film A (1-1) Preparation of composition A for forming photoalignment film The photo-alignment material (weight average molecular weight: 50,000, m:n = 50:50) having the following structure was produced according to the method described in JP 2021-196514 A. Two parts of the photo-alignment material and 98 parts of cyclopentanone (solvent) were mixed as components, and the resulting mixture was stirred at 80 ° C. for 1 hour to prepare a composition A for forming a photo-alignment film. Photoalignable materials: [ka]
[0240] (1-2) Preparation of polymerizable liquid crystal compound The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) having the structures shown below were prepared. The polymerizable liquid crystal compound (A1) was prepared in the same manner as described in JP-A-2019-003177. The polymerizable liquid crystal compound (A2) was prepared in the same manner as described in JP-A-2009-173893. Polymerizable liquid crystal compound (A1): [ka] Polymerizable liquid crystal compound (A2): [ka]
[0241] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (A1) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.
[0242] (1-3) Preparation of Retardation Film-Forming Composition A The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts of a leveling agent "BYK-361N" (manufactured by BM Chemie) and 3 parts of a photopolymerization initiator "Irgacure OXE-03" (manufactured by BASF Japan Ltd.) were added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration was 13%. The mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation film-forming composition A.
[0243] (1-4) Preparation of Retardation Film A Substrate A is a biaxially oriented polyethylene terephthalate (PET) film (Diafoil The composition A for forming a photo-alignment film was applied to a substrate (manufactured by Mitsubishi Plastics, Inc.) using a bar coater. The applied coating film was dried at 120°C for 2 minutes and then cooled to room temperature to form a dry coating. It was then irradiated with 100mJ of polarized ultraviolet light (313nm standard) using a UV irradiation device (SPOT CURE SP-9; manufactured by Ushio Inc.) to obtain a photo-alignment film A. The thickness of the photo-alignment film A was measured using an ellipsometer M-220 manufactured by JASCO Corporation and was 100nm.
[0244] The above-mentioned retardation film-forming composition A was applied onto the obtained photo-alignment film A using a bar coater to form a coating film. This coating film was dried by heating at 120°C for 2 minutes, and then cooled to room temperature to obtain a dried film. Next, using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.), the exposure amount was 500 mJ / cm2 in a nitrogen atmosphere. 2 The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation film A in which the polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface, thereby obtaining a laminate A consisting of substrate A / photo-alignment film A / retardation film A. The thickness of retardation film A was 2.0 μm as measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation.
[0245] The surface of the retardation film A of the laminate A was subjected to a corona treatment, and the laminate was attached to glass via a 25 μm-thick adhesive layer (manufactured by Lintec Corporation), and the substrate A was peeled off and removed. The in-plane retardation values for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated from Cauchy's dispersion formula obtained from the measurement results of the in-plane retardation values for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm. As a result, the in-plane retardation values were Re(450)=122 nm, Re(550)=140 nm, and Re(650)=144 nm, and the relationship between the in-plane retardation values at each wavelength was as follows: Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.03 (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.)
[0246] (2) Preparation of retardation film B (2-1) Preparation of composition B for forming alignment layer A composition B for forming an alignment film was obtained by adding 2-butoxyethanol to a commercially available alignment polymer, Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.), so that the solid content was 1%.
[0247] (2-2) Preparation of Retardation Film-Forming Composition B 100 parts of polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan Co., Ltd.), 0.1 parts of leveling agent "BYK-361N" (manufactured by BYK-Chemie Co., Ltd.), and 2.5 parts of photopolymerization initiator "Omnirad907" (manufactured by IGM Resin BV Co., Ltd.) were mixed. Furthermore, 400 parts of propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the resulting mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation film forming composition B. Polymerizable liquid crystal compound LC242: [ka]
[0248] (2-3) Preparation of retardation film B A cyclic olefin resin (COP) film (ZF14, manufactured by Zeon Corporation) was used as the substrate B, and one side of the film was subjected to corona treatment using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.), and the composition for forming an alignment film B was applied to the surface of the film using a bar coater and dried at 90° C. for 1 minute. The thickness of the resulting alignment film B was measured with a laser microscope and found to be 30 nm.
[0249] The retardation film-forming composition B was applied onto the obtained alignment film B using a bar coater and dried at 90° C. for 1 minute to obtain a dried film. The retardation film was exposed to light at a dose of 1000 mJ / cm 2 under a nitrogen atmosphere using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.). 2 The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation film B, thereby obtaining a laminate B consisting of a substrate B / alignment film B / retardation film B. The thickness of the retardation film B, as measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation, was 450 nm.
[0250] When the phase difference value was measured, Re(550) = 1 nm and Rth(550) = -75 nm. The laminate B had optical properties represented by nx ≈ ny < nz. Since the phase difference value of the COP at a wavelength of 550 nm is approximately 0, it has no influence on the optical properties.
[0251] (3) Fabrication of Phase Element 1 The retardation film A of laminate A and the retardation film B of laminate B were each subjected to corona treatment. An adhesive was applied to the corona-treated surface of either the retardation film A or the retardation film B, and laminate A and laminate B were bonded together. The above active energy ray-curable adhesive 1 was used as the adhesive. The corona treatment apparatus used was the AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was performed once using the above corona treatment apparatus under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. Ultraviolet rays were irradiated from the laminate A side to cure the active energy ray-curable adhesive 1, thereby forming an adhesive layer with a thickness of 1.5 μm. The ultraviolet rays were irradiated so that the UVA with a wavelength of 320 nm to 390 nm was 420 mJ / cm 2 As described above, a phase element 1 with a substrate composed of substrate A / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B / substrate B was fabricated.
[0252] [Fabrication of Phase Element 3] A phase element 3 was fabricated in the same manner as phase element 1, except that the active energy ray-curable adhesive 2 was used instead of the active energy ray-curable adhesive 1.
[0253] <Examples 1 to 17> The first protective layer selected from the above first protective layers 1 to 2, the polarizer selected from the above polarizers 1 to 2, the protective film selected from the above second protective layers 1 to 6, and the phase element 1 or 3 were bonded together. Then, an adhesive layer was laminated on the surface of the phase element 1 or 3 opposite to the second protective layer to obtain an optical laminate. Specifically, it is as follows.
[0254] A corona treatment was applied to one side of each of the surfaces of the first protective layer and the second protective layer (when a laminate having a second protective layer was used, the surface of the second protective layer of the laminate). A water-based adhesive was applied to one side of the polarizer, and the first protective layer was attached. A water-based adhesive was applied to the other side of the polarizer, and the second protective layer (or a laminate having a second protective layer) was attached. Then, the polarizing plate was obtained by drying. The water-based adhesive was prepared by dissolving 3 parts of carboxyl group-modified polyvinyl alcohol (trade name "KL-318" obtained from Kuraray Co., Ltd.) in 100 parts of water, and adding 1.5 parts of a polyamide epoxy-based additive, which is a water-soluble epoxy resin (trade name "Sumirez Resin 650 (30)" manufactured by Taoka Chemical Co., Ltd., an aqueous solution with a solid content concentration of 30%). As a result, a laminate X consisting of a first protective layer / adhesive layer / polarizer / adhesive layer / second protective layer was obtained. Here, when a laminate having a second protective layer was used, the laminate The structure X is a first protective layer / adhesive layer / polarizer / adhesive layer / second protective layer / support substrate.
[0255] Next, the surface of the second protective layer of the laminate X (when the laminate X has a supporting substrate, the surface from which the supporting substrate is peeled off) and the surface exposed by peeling off the substrate A of the retarder 1 or 3 were each subjected to a corona treatment. The corona treatment device used was AGF-B10 manufactured by Kasuga Electric Co., Ltd. The corona treatment was performed once using the corona treatment device under conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface of the laminate X and the corona-treated surface of the retarder 1 or 3 were bonded together via the pressure-sensitive adhesive layer 1. Thereafter, the substrate B of the retarder 1 or 3 was peeled off and removed to obtain a laminate Y including the first protective layer / adhesive layer / polarizer / adhesive layer / second protective layer / adhesive layer 1 / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B in this order. Finally, the pressure-sensitive adhesive layer 2 was laminated on the surface of the alignment film B side of the laminate Y to obtain an optical laminate. The types of the first protective layer, polarizer, second protective layer and retarder used in each example are shown in the "Layer structure" column in the table below.
[0256] <Examples 18 to 19> A laminate Z consisting of a first protective layer / adhesive layer / polarizer was obtained in the same manner as in Examples 1 to 17, except that the second protective layer was not laminated. One of the two cyclic polyolefin films having a thickness of 50 μm of the support substrate was changed to the laminate Z, and ultraviolet rays were irradiated from the cyclic polyolefin film side. A laminate Z' consisting of a first protective layer / adhesive layer / polarizer / second protective layer / support substrate was obtained in the same manner as in the preparation method of the second protective layer 8 or 9. Next, the surface exposed by peeling off the support substrate of the laminate Z' and the surface exposed by peeling off the substrate A of the phase shifter 3 were each subjected to a corona treatment (0.3 kW, treatment speed 3 m / min). The corona-treated surface of the laminate Z' and the corona-treated surface of the phase shifter 3 were bonded together via the pressure-sensitive adhesive layer 1. Thereafter, the base material B of the retarder 3 was peeled off to obtain a laminate including the first protective layer / adhesive layer / polarizer / second protective layer / adhesive layer 1 / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B in this order. Finally, the adhesive layer 2 was laminated on the surface of the laminate on the alignment film B side to obtain an optical laminate. The types of the first protective layer, polarizer, second protective layer, and retarder used in each example are shown in the "Layer configuration" column of the table below.
[0257] <Comparative Example 1> According to Example 1 of Patent Document 1, an optical laminate including, in this order, a first protective layer / adhesive layer / polarizer / adhesive layer / second protective layer / acrylic pressure-sensitive adhesive layer / retardation film (λ / 4 retardation plate) / adhesive layer / retardation film B (positive C plate) / acrylic pressure-sensitive adhesive layer was produced. The first protective layer corresponds to the first protective layer 1. The polarizer corresponds to the polarizer 2. The second protective layer is a triacetyl cellulose film having a thickness T2 of 20 μm ("ZRG20SL" manufactured by Fujifilm Corporation). This second protective layer is referred to as the second protective layer 7. The second protective layer 7 has a tensile modulus E2 of 830 MPa at a temperature of 85° C. and a moisture permeability of 1800 g / m 2 / 24hr, photoelasticity coefficient 8.8×10 -12 Pa -1 The retarder in Comparative Example 1 is referred to as retarder 2. The types of the first protective layer, polarizer, second protective layer and retarder used are shown in the "Layer configuration" column of the table below.
[0258] <Comparative Examples 2 and 3> An optical laminate including, in this order, first protective layer / adhesive layer / polarizer / pressure-sensitive adhesive layer 1 / retardation film A / adhesive layer / retardation film B / alignment film B / pressure-sensitive adhesive layer 2 was prepared in the same manner as in Examples 1 to 17, except that no second protective layer was laminated, and that the first protective layer, polarizer, and retarder shown in the table below were used. The types of the first protective layer, polarizer, and retarder used are shown in the "Layer configuration" column in the table below.
[0259] <Example 20> The first protection circuit was fabricated in the same manner as in Example 18, except that the phase shifter 1 was used instead of the phase shifter 3. An optical laminate was obtained that contained, in this order, the first protective layer, the polarizer, the second protective layer, the pressure-sensitive adhesive layer 1, the photo-alignment film A, the retardation film A, the adhesive layer, the retardation film B, the alignment film B, and the pressure-sensitive adhesive layer 2. The types of the first protective layer, the polarizer, the second protective layer, and the retarder used are shown in the "Layer configuration" column in the table below.
[0260] <Comparative Example 4> An optical laminate including first protective layer / adhesive layer / polarizer / second protective layer / pressure-sensitive adhesive layer 1 / photo-alignment film A / retardation film A / adhesive layer / retardation film B / alignment film B / pressure-sensitive adhesive layer 2 in this order was obtained in the same manner as in Example 7, except that second protective layer 7 was used instead of second protective layer 2. The types of first protective layer, polarizer, second protective layer, and retarder used are shown in the "Layer configuration" column in the table below.
[0261] The optical laminates produced in the Examples and Comparative Examples were evaluated for in-plane variation in retardation change and metal corrosion, and the results are shown in the following table.
[0262] [Table 1]
[0263] [Table 2]
[0264] [Table 3] [Explanation of symbols]
[0265] 5 polarizer, 10 first protective layer, 20 second protective layer, 30 retarder, 41 first adhesive layer, 42 second adhesive layer, 43 third adhesive layer, 50 adhesive layer, 16 laminate α, 17 adhesive mount, 18 cutout section.
Claims
1. An optical laminate including a first protective layer, a polarizer, a second protective layer, and a retarder in this order, the polarizer is a polyvinyl alcohol-based resin film having a thickness of 15 μm or less and having a dichroic dye adsorbed and oriented therein; When the tensile modulus of the second protective layer at a temperature of 85° C. is E2 [MPa] and the thickness is T2 [μm], the following formula (i): E2×T2≦16000 (i) An optical laminate that satisfies the above requirements.
2. The optical laminate according to claim 1, wherein the value of E2×T2 is 1850 or less.
3. The optical laminate according to claim 1 , wherein the retarder comprises a retardation film.
4. The following formula (ii): T2≦7 (ii) The optical laminate according to claim 1 , further satisfying the above.
5. The second protective layer has a moisture permeability of 1700 g / m 2 The optical laminate according to claim 1, wherein the heat treatment time is 24 hours or less.
6. The optical laminate according to claim 1 , wherein the second protective layer is made of a cyclic polyolefin resin.
7. The optical laminate according to claim 1 , wherein the second protective layer has an in-plane retardation value of 10 nm or less at a wavelength of 550 nm.
8. The optical laminate according to claim 1 , further comprising an adhesive layer between the polarizer and the second protective layer.
9. The optical laminate according to claim 1 , wherein the polarizer has a boron content of 0.5% by mass or more and 5.5% by mass or less.
10. When the tensile modulus of the first protective layer at a temperature of 85° C. is E1 [MPa] and the thickness is T1 [μm], the following formula (iii) is satisfied: 17000≦E1×T1≦40000 (iii) The optical laminate according to claim 1 ,
11. The optical laminate according to claim 1 , further comprising a pressure-sensitive adhesive layer laminated on a side of the retarder opposite to the second protective layer side.
12. When the tensile modulus at 23° C. of a laminate from a layer adjacent to the surface of the polarizer on the side of the phase shifter in the polarizer to a layer adjacent to the surface of the pressure-sensitive adhesive layer on the side of the phase shifter is E3 [MPa] and the thickness is T3 [μm], the following formula (iv) can be used: 7000≦E3×T3≦22000 (iv) The optical laminate according to claim 11, which satisfies the above.
13. An image display device comprising the optical laminate according to any one of claims 1 to 12.
Citation Information
Patent Citations
Polarizing plate and display device
JP2021121862A